A pilot study on real-time monitoring of canine responses to exercise - Melissa J. Starling; Paul P. Breen; Carolyn Broderick; Cameron E.F. Clark; Barry Flower; Clara Grazian; Titus Jayarathna; Ollie Jay; Philip H.W. Leong; Sabrina Lomax; Scott A. Sisson; Paul Damien McGreevy (Applied Animal Behaviour Science, 2026)

Water Quality Impacts from Legacy Mining and Geothermal Groundwater in a Fault-Controlled Carbonate-Hosted Metal Mining District - Cameron P. Cordner; Gregory T. Carling; Barry R. Bickmore; Kevin A. Rey; Diego P. Fernandez (Water, Air, & Soil Pollution, 2026)

Sustainable microalgal feed formulations for functional and omega-3-enriched eggs in poultry production - Daniela Diaz Mac Adoo; María Teresa Mata; Maria P. Kaltsidi; Paula Ardiles; Niel Jensen; Victoria Cruz-Balladares; Henry Cameron; Vladimir Avalos; Francisco Sepúlveda-Sánchez; Jennifer Palma; Carlos Riquelme (Algal Research, 2026)

Metagenomic sequencing provides insight into pathogenic and related benign microbes in ticks collected from pastured cattle - Cameron J. Osborne; Anna Grace Deakins; Koray Ergunay; Brian P. Bourke; Yvonne-Marie Linton; Le Jiang; John P. Grieco; Nicole L. Achee; Emily G. McDermott (Veterinary Microbiology, 2026)

Consequential life cycle assessment of European livestock systems: current practices, limitations, and priorities - Dengsheng Sun; Marie Trydeman Knudsen; Thomas Ponsioen; Ricardo Teixeira; Alina Chervinska; Mariana Raposo; Rahela Lucić; Mali Gravell; Nicholas Davison; Lewis Cameron; Sally Westaway; Aurélie Wilfart; et al. (Journal of Industrial Ecology, 2026)
A systems-level understanding of livestock production and its environmental consequences is essential for informing sustainability transitions and evidence-based policy in Europe. While life cycle assessment (LCA) is widely applied in this context, the use of consequential LCA (CLCA), which aims to capture market-mediated and structural system responses, remains comparatively limited. This study provides a critical synthesis of CLCA applications in European livestock systems through a PRISMA-guided systematic literature review complemented by an expert workshop. Twenty-three studies met the inclusion criteria, spanning multiple livestock groups, regions, and modelling approaches. Scenario development was dominated by technical or management-oriented adjustments, with limited use of optimisation-based, narrative, or policy-driven frameworks capable of exploring transformative system changes. Inventory construction typically relied on Ecoinvent, supplemented where necessary by experimental datasets, expert elicitation, survey data, or outputs from economic models. Most studies focused on midpoint indicators, and although uncertainty analysis was commonly included, its implementation was inconsistent across studies. Overall, most of the reviewed CLCA applications remain focused on incremental improvements within existing systems, limiting their ability to assess the consequences of more profound system transitions. Key limitations include both methodological challenges (particularly in scenario formulation and the representation of system-wide responses) and data gaps, notably the limited availability of regionally specific inventory data for marginal processes and endpoint characterisation factors. We recommend that future CLCAs adopt more structured and forward-looking scenario development approaches, strengthen inventory construction through updated and localised datasets, and consider the incorporation of both midpoint and endpoint indicators, while clearly acknowledging the limitations of both approaches. In addition, the systematic application of sensitivity and scenario-based uncertainty analysis is essential for assessing robustness. Addressing these practical and methodological dimensions will enhance the contribution of CLCA to analysing sustainability transitions of European livestock systems.

Formulation and characterization of exenatide-loaded PLGA microspheres prepared by coacervation - Cameron White; Steven P. Schwendeman (Drug Delivery and Translational Research, 2026)

Erwinia amylovora amino acid auxotrophy and epiphytic growth on apple stigmas - Neil P. Schultes; Judith P. Sinn; Eric S. Swenson; Louis Orifice; Cameron Ryan; Timothy W. McNellis (Physiological and Molecular Plant Pathology, 2026)

Correction: The potent human CAR activator CITCO is a non-genotoxic hepatic tumour-promoting agent in humanised constitutive androstane receptor mice but not in wild-type animals - C. J. Henderson; A. W. McLaren; A. K. MacLeod; D. Lin; A. R. Cameron; L. R. Chatham; J. Moggs; F. Inesta‑Vaquera; John P. Thomson; Richard R. Meehan; P. Chakravarty; M. Schwarz; et al. (Archives of Toxicology, 2026)

Gait Retraining with Realtime Feedback May Reduce Pain and Improve Function in Runners: A Systematic Review - Michael S. Crowell; Jamie B. Morris; Ryan C. Peterson; Michael P. DiLullo; Shane A. McKeon; Cameron S. Young (Journal of Science in Sport and Exercise, 2026)
Purpose Running-related lower extremity injuries are common and often linked to modifiable biomechanical factors. Gait retraining (GR) using real-time feedback (RTF) has emerged as a potential intervention to alter running biomechanics and reduce pain, but the clinical effectiveness in injured runners has not been determined. The purpose of this study was to evaluate the effectiveness of GR with RTF on lower extremity pain and function in runners. Methods A systematic search of 4 databases identified studies involving runners over age 18 with lower extremity pain who received GR with RTF. Studies were assessed for methodological quality using National Institutes of Health Quality Assessment Tools. Results Nine studies met inclusion criteria. There were 5 level II studies (2 good, 2 fair, 1 poor quality) and 4 level IV studies (1 good, 3 fair quality). Two RCTs found significant reductions in pain between groups. Two RCTs found no between-group differences but did report significant improvements within groups. All RCTs and case series showed within-group pain reductions (Visual Analogue Scale decrease range: 2.2–5.0; Numerical Pain Rating Scale: 2.1–5.9). Improvements in self-reported function (Lower Extremity Functional Scale, Anterior Knee Pain Scale) were observed in all 5 studies that measured functional outcomes. Protocols varied but typically involved 8–10 sessions over 4–6 weeks using verbal, visual, or auditory feedback to promote a non-rearfoot strike and increased step rate. Conclusion Low certainty evidence supports GR with RTF to reduce pain in runners. While within-group improvements often exceeded clinically meaningful thresholds, small sample sizes, heterogeneity, and limited high-quality trials constrained definitive conclusions and did not allow for meta-analysis. Larger, methodologically rigorous studies are needed to optimize and validate GR protocols using RTF.

Sex-associated variables – A framework for neurotoxicology - Cameron P. Hamson; Morgan L. Atkinson; Troy A. Roepke (NeuroToxicology, 2026)

Evaluating the validity of using sea surface temperature as an alternative to bottom temperature in American lobster habitat suitability modeling - Xiangyan Yang; Robyn Linner; Cameron Hodgdon; Jacob P. Kritzer; George Maynard; Erin Pelletier; Yong Chen (Progress in Oceanography, 2026)

Reptile demographics on paved roads in protected (Hluhluwe-iMfolozi Park, iSimangaliso Wetland Park) and unprotected areas (Giba Rural Community) in northeastern KwaZulu-Natal, South Africa - Cameron T. Cormac; Cormac Price; Jarryd P. Streicher; Colleen T. Downs (Journal for Nature Conservation, 2025)

State level differences in life expectancy and lifespan inequality: Is it a matter of socioeconomic inequalities? - M.D.J.W. Wijesinghe; Michael P. Cameron; Susan Olivia; Les Oxley (Economics & Human Biology, 2025)

Annual Temperature Range Drives Thermal Breadth of Freshwater Insects Across Multiple Spatial Scales - Beatrice S. Dewenter; Darren P. Giling; Alisha A. Shah; Jane Hughes; N. LeRoy Poff; Cameron K. Ghalambor; W. Chris Funk; Stephanie Bristow; Ross M. Thompson; Ben J. Kefford (Ecology Letters, 2025)
Thermal breadth ( T br ) is a critical trait influencing organisms' response to climate change. Three hypotheses seek to explain interspecific and interpopulation variation in T br , each relying on a different temperature driver: Climate Variability Hypothesis (CVH)–annual temperature range; Thermal Constraints Hypothesis (TCH)–mean annual temperature; and Diel Narrowing Hypothesis (DNH)–mean diel temperature range. We test these hypotheses by measuring the T br of freshwater insects (Ephemeroptera, Plecoptera and Trichoptera) along elevational gradients in the Americas and Australia, contrasting warm and cool adapted species from low climate variability tropical regions and high climate variability temperate regions. We find strong and consistent support for the CVH, limited support for the TCH (in two of four regions) and no support for the DNH. We conclude that T br of freshwater insects is better explained by annual temperature variability, rather than high temperatures or diel temperature variability.

Quantitative PCR detection of endangered diamond darter Crystallaria Cincotta in environmental DNA: employing locked nucleic acids and blocking probe for specificity - Andrew P. Kinziger; Cameron Layne; Stuart Welsh (Conservation Genetics Resources, 2025)

Correction: The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Gene Expression Associated With Behaviour Manipulation in Wood Ants Infected With Larval Lancet Fluke, Dicrocoelium dendriticum - Chen‐Hua Li; Cameron P. Goater; James D. Wasmuth (Molecular Ecology, 2025)
Many ant species show dramatic shifts in behaviour when infected with parasites, but the molecular basis of these behavioural changes is not well understood. An example is the wood ant, Formica aserva , which serves as an intermediate host for the lancet liver fluke, Dicrocoelium dendriticum . Infected ants leave their nests during the cool hours of the day, ascend a flower and then attach themselves to a petal with their mandibles. Attached ants remain affixed to an inflorescence overnight, after which they detach, descend the plant and return to their nest. Unless eaten by a grazing mammal (the obligate next host), infected ants repeat this attach‐and‐detach cycle for the rest of the summer. We used transcriptomics to decipher the potential molecular mechanisms that underlie this reversible behaviour manipulation. Using naturally infected ants, we recreated the manipulation cycle in the laboratory and then evaluated messenger RNA from ant brains at four contrasting phases of manipulation. Among these phases, we found a total of 1349 transcripts differentially expressed between infected and uninfected ant brains. Many of these transcripts are involved in cell signalling pathways, including odorant, gustatory, vision, circadian rhythm and the production of biogenic monoamines and hormones. Metabolism, protein management and DNA repair functions might also play a role at different phases of manipulation. Our combined results are consistent with the idea that the mechanism(s) leading to the attach/detach/repeat sequence of behaviours of fluke‐infected ants is multifaceted, involving much more than temperature‐dependent contraction/relaxation of the mandibular muscles.

Pesticide and Pathogen Exposure Causes Idiosyncratic Gene Expression Responses Across Four Diverse North American Bumble Bee Species - Rubén Martín‐Blázquez; Sydney A. Cameron; Austin C. Calhoun; James P. Strange; Ben M. Sadd (Molecular Ecology, 2025)
Bumble bee ( Bombus Latreille) populations of certain species have declined precipitously in North America over several decades. Hypotheses for declines include exposure to the pathogen Nosema bombi and neonicotinoid pesticides. Importantly, populations of some bumble bee species remain stable despite their presumed exposure to these same stressors. We hypothesise that declining and stable species exhibit distinct responses to N. bombi and neonicotinoids, detectable as differential gene expression profiles. To test this, we exposed larvae of Bombus occidentalis (declining) and B. impatiens (stable) to N. bombi and to the neonicotinoid imidacloprid, plus a combination of both. RNA‐seq analysis revealed almost no overlap between these species in gene expression responses to the individual stressors. There was more overlap of differentially expressed genes for the combined‐stressor condition, but hundreds of genes still showed species‐specific expression differences. To test whether the differential molecular responses could be associated with declining and stable species, we performed quantitative PCR on 20 selected genes, adding two additional species B. terricola (declining) and B. griseocollis (stable). These responses did not separate out by species decline status; each of the four species exhibit species‐specific responses. Overall, these results highlight that generalising mechanisms and causes of decline across different species may be misleading, as diverse species respond molecularly in a species‐specific manner to particular environmental stressors.

Priming the decomposition of cover crop residues in no-till organic cropping systems - Delaney A. Sondag; Amélie C.M. Gaudin; Jeffery P. Mitchell; Cameron M. Pittelkow (Agriculture, Ecosystems & Environment, 2025)

The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Interspecific eavesdropping by birds on a keystone mammal improves antipredator behaviour - R. Andrew Dreelin; Holly P. Jones; Daniel A. Gutiérrez-Carrillo; Cameron Piper; Brooke D. Goodman; Cayle J.R. Cross; Xander R. Vitarelli; Coley L. Turner; Adeline R. Wichman; Lily G. Austin; Andy J. Boyce (Animal Behaviour, 2025)

SRM survey and membership shifts demonstrate “change on the range” - Jamie Dahl; Julie E. Larson; Cameron Duquette; María E. Fernández-Giménez; Evan P. Tanner; Devii Rao; Gene Gloeckner (Rangelands, 2025)

The Cerebellar Neuropsychiatric Rating Scale in the Spinocerebellar Ataxias - Anna L. Burt; Maureen P. Daly; Janet C. Sherman; Jeremy D. Schmahmann; Susan L. Perlman; Liana S. Rosenthal; Sheng-Han Kuo; Tetsuo Ashizawa; Theresa Zesiewicz; Cameron Dietiker; Puneet Opal; Antoine Duquette; et al. (The Cerebellum, 2025)

The applicability of regional red list assessments for soil invertebrates: first assessment of five native earthworm species in Canada - Helen R. P. Phillips; George G. Brown; Sam W. James; Jérôme Mathieu; John Warren Reynolds; Maheshi E. Dharmasiri; Claire L. Singer; Maria J. I. Briones; Heather C. Proctor; Erin K. Cameron (Biodiversity and Conservation, 2025)
Earthworms (Annelida: Clitellata: Crassiclitellata) are prominent members of the soil community, important to many ecosystem functions. Despite this, and like many other soil invertebrates, they are rarely considered in conservation assessments, including the International Union for Conservation of Nature (IUCN) Red List assessments used to assess species’ extinction risk. To investigate the applicability of the IUCN Regional Red Listing protocol to soil invertebrates, we assessed the conservation status of five earthworm species native to Canada using this protocol and all available occurrence records. In Canada, no earthworm species have yet been assessed by the Committee on the Status of Endangered Wildlife in Canada (COSEWIC). Due to the lack of data on population sizes and their trends, all five species were assessed using their Extent of Occurrence (EOO) (Criterion B). One species was assessed as Vulnerable ( Arctiostrotus vancouverensis) , two were assessed in non-threatened categories ( A. perrieri and Sparganophilus tamesis ), and two were assessed as Data Deficient ( A. fontinalis and Toutellus oregonensis ). For the majority, the main threats identified were the continuing loss of potential habitat due to land conversion and resource exploitation, as well as the effects of climate change. Increasing the amount of data, including but not limited to distribution and habitat preferences, would make the assessment process easier and status decisions better supported. By undertaking regional assessments for five native earthworm species in Canada, we show that Regional Red List assessments are feasible for soil invertebrates.

The potent human CAR activator CITCO is a non-genotoxic hepatic tumour-promoting agent in humanised constitutive androstane receptor mice but not in wild-type animals - C. J. Henderson; A. W. McLaren; A. K. MacLeod; D. Lin; A. R. Cameron; L. R. Chatham; J. Moggs; F. Inesta-Vaquera; John P. Thomson; Richard R. Meehan; P. Chakravarty; M. Schwarz; et al. (Archives of Toxicology, 2025)
A large number of drugs and compounds produced by the chemical and agrochemical industry, often referred to as ‘non-genotoxic carcinogens’ (NGC), score as tumour promotors in rodent models. It is unclear whether these compounds act similarly in humans. The most extensively investigated compounds have been the anti-convulsive drugs, phenobarbital (PB), and phenytoin. Liver tumours induced by PB are dependent upon the activation of the constitutive androstane receptor (CAR). However, marked species differences in CAR activation by exogenous chemicals exist with some being much more potent activators of human CAR, e.g., 6-(4-chlorophenyl)imidazo[2,1-β][1,3]thiazole-5-carbaldehyde-O-(3,4-dichlorobenzyl)oxime (CITCO). We have compared CITCO-induced tumour formation in the livers of mice in which murine CAR has been replaced with its human counterpart. Our findings reveal that CITCO-dependent liver tumours are only formed in mice-expressing human CAR and not in wild-type animals. In addition, contrary to one of the proposed mechanisms of NGC carcinogenicity, we show that CITCO did not induce a hyperplastic response in the liver of the humanised mice. These data raise some key questions about the mechanism of action of NGCs and identify the limitations of current rodent carcinogenicity test systems in relation to risk assessment.

Multi‐endmember mixing and primary productivity drive carbonate system variability on a highly heterogeneous, shallow productive bank - F. Dylan Titmuss; Jennie E. Rheuban; Louise P. Cameron; Jonathan H. Grabowski; Zhaohui Aleck Wang (Limnology and Oceanography, 2025)
This study presents the first high‐resolution spatial analysis of carbonate chemistry on Georges Bank, a highly productive shallow bank located at the southeastern edge of the Gulf of Maine. Despite numerous studies on the hydrography, nutrient chemistry, and biology, regional carbonate chemistry remains unexplored, in particular for near‐bottom conditions. Observations from cruises in May and October 2021 were used to identify multi‐endmember mixing, and a Bayesian mixing model was applied to temperature and salinity to separate water mass mixing from non‐conservative drivers such as net community production, air–sea exchange, and other biogeochemical processes/errors. Major findings from this study indicate that carbonate chemistry is highly heterogeneous and driven by multi‐endmember mixing, although biological production and respiration were notable while air–sea CO 2 exchange was minimal. Five water masses with unique carbonate chemistry were observed that varied by season and with depth, showing complexity that is uncommon in other regions along the US Atlantic coast. In both cruises, a Warm Slope Water intrusion was identified at depth that contained a strong signal of CaCO 3 dissolution during the October cruise, observed in situ for the first time in this region. Under a high emissions scenario, our results suggest that much of the bank's bottom waters may become undersaturated with respect to aragonite by 2100. Together, these findings suggest that the in situ dissolution observed may only worsen with future ocean acidification, with potentially significant implications for ecologically and economically important shellfish species on Georges Bank.

Sedimentological reconstruction of Glan-y-môr Isaf, North Wales: A model for the formation of stratified subglacial till assemblages from glaciolacustrine deposits - Cameron J. Powell; Rachel P. Oien (Quaternary Science Reviews, 2025)

Review of the techniques for estimating population size of Adélie penguins (Pygoscelis adeliae) - Alexandra J. Strang; Elissa Z. Cameron; Dean P. Anderson; Esme Robinson; Michelle A. LaRue (Polar Biology, 2025)
Monitoring of sentinel species provides insight into the ecosystems in which they live. In the Southern Ocean, penguins are one such indicator species, where only a limited number of colonies have been monitored extensively for decades around Antarctica. As the Southern Ocean warms and commercial fishing continues, the need for expansion of population monitoring has become paramount. Using Adélie penguins ( Pygoscelis adeliae ) as a model species, we reviewed methods to estimate colony size including ground and aerial (occupied and unoccupied aircraft) assessment and satellite imagery, with an aim of understanding costs and benefits of each method to inform their future use. Ground assessment includes physically taxing field counts of individuals or nests and was historically the only method used to count penguins in Antarctica. Aerial assessments via occupied and unoccupied aircraft have expanded the spatial extent of monitoring for remote and logistically challenging environments such as Antarctica. Combined with aerial assessment, the more recent use of very high-resolution satellite imagery (VHR) has further expanded Adélie penguin monitoring into previously inaccessible areas. Adélie penguin breeding colonies can be monitored using VHR imagery through the area of their guano stain as a proxy for the number of breeding pairs. Our review provides an overview of the monitoring techniques for Adélie penguins in Antarctica and provides direction for future use and development.

Status of truffle science and cultivation in North America - Mark D. Coleman; Shannon Berch; Gregory Bonito; Brian Allen; Ellie Andrews; Elva T. Arechiga Carvajal; Stephen P. Cook; Cameron D’Amours; Roberto Garibay-Orijel; Gonzalo Guevara; Patrick Hatzenbuehler; Barbara Hawkins; et al. (Plant and Soil, 2025)
Background Truffles are subterranean fungal fruiting bodies that are highly prized for their culinary value. Cultivation of truffles was pioneered in Europe and has been successfully adapted in temperate regions throughout the globe. Truffle orchards have been established in North America since the 1980s, and while some are productive, there are still many challenges that must be overcome to develop a viable North American truffle industry. These challenges include extended delays between establishment and production, comparatively low yields, high spatial heterogeneity in yield distribution, and orchard contamination with lower-value truffle fungi. Aim Here we review known requirements for truffle production including necessary environmental conditions, reproductive biology, and effective agronomic practices. Content We consider the potential limitations of importing exotic host-fungal associations into North America where there is already a rich community of competing ectomycorrhizal fungi, host pests and pathogens. We also describe the status of the North American truffle industry with respect to market potential, including production costs, pricing, and biological and socioeconomic risk factors. A critical aspect of modern trufficulture involves monitoring with genetic tools that supply information on identity, abundance and distribution of fungal symbionts, abundance of competitive and contaminating fungi, and insight into the interactions between fungal mating types that are fundamental to the formation of truffle primordia. Implications Cultivation of the ectomycorrhizal truffle symbiosis requires application of pragmatic agronomic practices, adopting rigorous quality control standards, and an understanding of fungal biology, microbiology, and molecular biology. Consequently, significant interdisciplinary collaboration is crucial to further develop the North American truffle industry.

Modeling the advective supply of Calanus finmarchicus to Stellwagen Bank as an indicator of sand lance foraging habitat, and the climate vulnerability of a National Marine Sanctuary - Cameron R. S. Thompson; Isabel A. Honda; Jacob P. Kritzer; Jackie Motyka; Jeffrey A. Runge; Rubao Ji (Frontiers in Marine Science, 2025)
The northern sand lance ( Ammodytes dubius ), a key species in the food web supporting the Stellwagen Bank National Marine Sanctuary (SBNMS), feeds primarily on the lipid-rich copepod Calanus finmarchicus . Climate change poses a significant threat to this dynamic, as C. finmarchicus populations are at the southern edge of their subarctic distribution and are vulnerable to warming waters and changing oceanographic conditions. Declines in the advective supply of C. finmarchicus to Stellwagen Bank could adversely affect sand lance populations and, consequently, the ecological and economic resources that depend on them. To quantify the connectivity between SBNMS and potential sources of C. finmarchicus , we used the Finite-Volume Community Ocean Model (FVCOM) coupled with Lagrangian particle tracking over the years 1978 to 2016. Numerical experiments revealed that Stellwagen Bank is highly connected to upstream areas in the Maine Coastal Current (MCC), where existing time series monitoring stations observe C. finmarchicus populations. The connectivity exhibited strong seasonal patterns, with peak connectivity occurring during spring and early summer, aligning with the sand lance feeding period on C. finmarchicus . We found significant interannual variability, influenced by changes in the strength of the MCC and circulation patterns in the western Gulf of Maine. Years with stronger MCC flow showed higher connectivity and a greater potential supply of C. finmarchicus particles to Stellwagen Bank. Conversely, periods of reduced flow corresponded with decreased connectivity, potentially limiting the availability of C. finmarchicus to sand lance populations. Meanwhile, observations from drifters and buoys since 2001 have documented decreases in MCC current speed which has been linked to a climate driven strengthening of southwesterly winds. These findings underscore the importance of pelagic habitat connectivity in assessing the climate vulnerability of marine protected areas (MPAs) like SBNMS. Furthermore, monitoring C. finmarchicus populations at upstream time series stations can provide information on downstream foraging habitat in MPAs, and potentially in other vulnerable areas of ecological and socioeconomic interest. By incorporating these indicators of connectivity and upstream C. finmarchicus population abundance into decision support tools, Sanctuary managers and stakeholders can make informed decisions to mitigate potential climate impacts.

Copper resistance in Legionella pneumophila: Role of genetic factors and host cells - Gillian Cameron; Sébastien P. Faucher (Science of The Total Environment, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Sport-Specific Recovery Trajectories for NCAA Collegiate Athletes Following Concussion - Spencer W. Liebel; Kathryn L. Van Pelt; Paul F. Pasquina; Thomas W. McAllister; Michael A. McCrea; Steven P. Broglio; Scott Anderson; Holly Benjamin; Thomas Buckley; Kenneth Cameron; Sara Chrisman; James Clugston; et al. (Annals of Biomedical Engineering, 2024)

Initial Mild Traumatic Brain Injury Characteristics and Recovery Patterns Among Females Across the United States Military Service Academies: A Report from the NCAA-DoD CARE Consortium - Landon B. Lempke; Elsa Ermer; Adrian J. Boltz; Jaclyn Caccese; Thomas A. Buckley; Kenneth L. Cameron; Sara P. D. Chrisman; Christopher D’Lauro; James T. Eckner; Carrie Esopenko; Tamerah N. Hunt; Divya Jain; et al. (Annals of Biomedical Engineering, 2024)

Changes in soil N2O emissions and nitrogen use efficiency following long-term soil carbon storage: Evidence from a mesocosm experiment - Lindsey A. Kelley; Zhenglin Zhang; Santiago Tamagno; Mark E. Lundy; Jeffrey P. Mitchell; Amélie C.M. Gaudin; Cameron M. Pittelkow (Agriculture, Ecosystems & Environment, 2024)

Semi-automated system for capturing and removing invasive carp during seasonal migrations - Przemyslaw G. Bajer; M. Vincent Hirt; Cameron P. Swanson; Emil Kukulski; Matthew Kocian (Biological Invasions, 2024)

Environmental behaviour of iron and steel slags in coastal settings - Alex L. Riley; James Cameron; Ian T. Burke; Patrizia Onnis; John M. MacDonald; Catherine J. Gandy; Richard A. Crane; Patrick Byrne; Sean Comber; Adam P. Jarvis; Karen A. Hudson-Edwards; William M. Mayes (Environmental Science and Pollution Research, 2024)
Iron and steel slags have a long history of both disposal and beneficial use in the coastal zone. Despite the large volumes of slag deposited, comprehensive assessments of potential risks associated with metal(loid) leaching from iron and steel by-products are rare for coastal systems. This study provides a national-scale overview of the 14 known slag deposits in the coastal environment of Great Britain (those within 100 m of the mean high-water mark), comprising geochemical characterisation and leaching test data (using both low and high ionic strength waters) to assess potential leaching risks. The seaward facing length of slag deposits totalled at least 76 km, and are predominantly composed of blast furnace (iron-making) slags from the early to mid-20th Century. Some of these form tidal barriers and formal coastal defence structures, but larger deposits are associated with historical coastal disposal in many former areas of iron and steel production, notably the Cumbrian coast of England. Slag deposits are dominated by melilite phases (e.g. gehlenite), with evidence of secondary mineral formation (e.g. gypsum, calcite) indicative of weathering. Leaching tests typically show lower element (e.g. Ba, V, Cr, Fe) release under seawater leaching scenarios compared to deionised water, largely ascribable to the pH buffering provided by the former. Only Mn and Mo showed elevated leaching concentrations in seawater treatments, though at modest levels (<3 mg/L and 0.01 mg/L, respectively). No significant leaching of potentially ecotoxic elements such as Cr and V (mean leachate concentrations <0.006 mg/L for both) were apparent in seawater, which micro-X-Ray Absorption Near Edge Structure (μXANES) analysis show are both present in slags in low valence (and low toxicity) forms. Although there may be physical hazards posed by extensive erosion of deposits in high-energy coastlines, the data suggest seawater leaching of coastal iron and steel slags in the UK is likely to pose minimal environmental risk.

Modification of pectin with high-pressure processing treatment of fresh orange peel before pectin extraction: Part II. The effects on gelling capacity and emulsifying properties of pectin - Wei Zhao; Yixiang Xu; Christina Dorado; Jinhe Bai; Hoa K. Chau; Arland T. Hotchkiss; Madhav P. Yadav; Randall G. Cameron (Food Hydrocolloids, 2024)

Structure-activity relationships for alkyl-phenanthrenes support two independent but interacting synergistic models for PAC mixture potency - John P. Incardona; Tiffany L. Linbo; James R. Cameron; Nathaniel L. Scholz (Science of The Total Environment, 2024)

The Cerebellar Cognitive Affective/Schmahmann Syndrome Scale in Spinocerebellar Ataxias - Louisa P. Selvadurai; Susan L. Perlman; Tetsuo Ashizawa; George R. Wilmot; Chiadi U. Onyike; Liana S. Rosenthal; Vikram G. Shakkottai; Henry L. Paulson; Sub H. Subramony; Khalaf O. Bushara; Sheng-Han Kuo; Cameron Dietiker; et al. (The Cerebellum, 2024)

Impact of organic matter on transformation during thermal remediation of pyrene-contaminated substrates - Cameron P. Oden; Charles J. Werth; Benjamin A. Kienzle; Lynn E. Katz (Science of The Total Environment, 2024)

Holocene climate and catchment change inferred from the geochemistry of Lashmars Lagoon, Kangaroo Island (Karti/Karta), southern Australia - Lucinda Cameron Duxbury; Lluka Yohanni Johns-Mead; Haidee Cadd; Alexander Francke; Stefan C. Löhr; Wallace Boone Law; Linda Armbrecht; Philip Anthony Hall; Atun Zawadzki; Geraldine E. Jacobsen; Patricia S. Gadd; David P. Child; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Genomics‐informed conservation units reveal spatial variation in climate vulnerability in a migratory bird - Caitlin V. Miller; Christen M. Bossu; James F. Saracco; David P. L. Toews; Clark S. Rushing; Amélie Roberto‐Charron; Junior A. Tremblay; Richard B. Chandler; Matthew G. DeSaix; Cameron J. Fiss; Jeff L. Larkin; Samuel Haché; et al. (Molecular Ecology, 2024)
Identifying genetic conservation units (CUs) in threatened species is critical for the preservation of adaptive capacity and evolutionary potential in the face of climate change. However, delineating CUs in highly mobile species remains a challenge due to high rates of gene flow and genetic signatures of isolation by distance. Even when CUs are delineated in highly mobile species, the CUs often lack key biological information about what populations have the most conservation need to guide management decisions. Here we implement a framework for CU identification in the Canada Warbler ( Cardellina canadensis ), a migratory bird species of conservation concern, and then integrate demographic modelling and genomic offset to guide conservation decisions. We find that patterns of whole genome genetic variation in this highly mobile species are primarily driven by putative adaptive variation. Identification of CUs across the breeding range revealed that Canada Warblers fall into two evolutionarily significant units (ESU), and three putative adaptive units (AUs) in the South, East, and Northwest. Quantification of genomic offset, a metric of genetic changes necessary to maintain current gene–environment relationships, revealed significant spatial variation in climate vulnerability, with the Northwestern AU being identified as the most vulnerable to future climate change. Alternatively, quantification of past population trends within each AU revealed the steepest population declines have occurred within the Eastern AU. Overall, we illustrate that genomics‐informed CUs provide a strong foundation for identifying current and future regional threats that can be used to inform management strategies for a highly mobile species in a rapidly changing world.

Response to competing conspecific cues depends on social context in the honey bee Apis mellifera - Rebecca R. Westwick; Gavin P. Brackett; Cameron E. Brown; Bethany J. Ison; Clare C. Rittschof (Animal Behaviour, 2023)

Bioretention filtration prevents acute mortality and reduces chronic toxicity for early life stage coho salmon (Oncorhynchus kisutch) episodically exposed to urban stormwater runoff - Jenifer K. McIntyre; Julann Spromberg; James Cameron; John P. Incardona; Jay W. Davis; Nathaniel L. Scholz (Science of The Total Environment, 2023)

Light to moderate long-term grazing enhances ecosystem carbon across a broad climatic gradient in northern temperate grasslands - Edward W. Bork; Daniel B. Hewins; Eric G. Lamb; Cameron N. Carlyle; Mark P. Lyseng; Scott X. Chang; Michael J. Alexander; Walter D. Willms; Majid Iravani (Science of The Total Environment, 2023)

Wastewater discharges alter microbial community composition in surface waters of the canadian prairies - Milena Esser; Cameron Hoggarth; Helen Baulch; Jonathan K. Challis; Yuwei Xie; John P. Giesy; Markus Hecker; Markus Brinkmann (Chemosphere, 2023)

Sustained ICP Elevation Is a Driver of Spatial Memory Deficits After Intraventricular Hemorrhage and Leads to Activation of Distinct Microglial Signaling Pathways - Chloe H. Puglisi; Bradley P. Ander; Catherine Peterson; Janet A. Keiter; Heather Hull; Cameron W. Hawk; Venina S. Kalistratova; Ali Izadi; Gene G. Gurkoff; Frank R. Sharp; Ben Waldau (Translational Stroke Research, 2023)

Modelling growth of Bacillus cereus in paneer by one-step parameter estimation - Dipon Sarkar; Ian Hunt; Cameron Macdonald; Bing Wang; John P. Bowman; Mark L. Tamplin (Food Microbiology, 2023)

A mechanistic framework for studying indirect effects of large vertebrate herbivores on pollinators - Katherine C. Kral-O’Brien; Bethany Roberton; Cameron A. Duquette; Torre J. Hovick; Jason P. Harmon (Arthropod-Plant Interactions, 2023)

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

Improved enzyme thermal stability, loading and bioavailability using alginate encapsulation - Yilun Weng; Supun Ranaweera; Da Zou; Anna P. Cameron; Xiaojing Chen; Hao Song; Chun-Xia Zhao (Food Hydrocolloids, 2023)

A hidden cost of single species management: Habitat-relationships reveal potential negative effects of conifer removal on a non-target species - Nicholas J. Van Lanen; Adrian P. Monroe; Cameron L. Aldridge (Biological Conservation, 2023)

A genome-wide association study of frailty identifies significant genetic correlation with neuropsychiatric, cardiovascular, and inflammation pathways - Yixuan Ye; Rommell B. Noche; Natalia Szejko; Cameron P. Both; Julian N. Acosta; Audrey C. Leasure; Stacy C. Brown; Kevin N. Sheth; Thomas M. Gill; Hongyu Zhao; Guido J. Falcone (GeroScience, 2023)

Minimal adaptation of the molecular regulators of mitochondrial dynamics in response to unilateral limb immobilisation and retraining in middle-aged men - Chantal A. Pileggi; Christopher P. Hedges; Randall F. D’Souza; Brenan R. Durainayagam; Nina Zeng; Vandre C. Figueiredo; Anthony J. R. Hickey; Cameron J. Mitchell; David Cameron-Smith (European Journal of Applied Physiology, 2023)

An efficient indirect plant regeneration from shoot apical meristem (SAM) derived embryogenic callus of Miscanthus × giganteus - Karolina Sobańska; Piotr Jedryszek; Cameron Kern; Aneta Basińska-Barczak; Tomasz Pniewski; Stephen P. Long (Biocatalysis and Agricultural Biotechnology, 2023)

In vitro degradation and erosion behavior of commercial PLGAs used for controlled drug delivery - Jennifer Walker; Jason Albert; Desheng Liang; Jing Sun; Richard Schutzman; Raj Kumar; Cameron White; Moritz Beck-Broichsitter; Steven P. Schwendeman (Drug Delivery and Translational Research, 2023)

Accuracy, realism and general applicability of European forest models - Mats Mahnken; Maxime Cailleret; Alessio Collalti; Carlo Trotta; Corrado Biondo; Ettore D'Andrea; Daniela Dalmonech; Gina Marano; Annikki Mäkelä; Francesco Minunno; Mikko Peltoniemi; Volodymyr Trotsiuk; et al. (Global Change Biology, 2022)
Forest models are instrumental for understanding and projecting the impact of climate change on forests. A considerable number of forest models have been developed in the last decades. However, few systematic and comprehensive model comparisons have been performed in Europe that combine an evaluation of modelled carbon and water fluxes and forest structure. We evaluate 13 widely used, state‐of‐the‐art, stand‐scale forest models against field measurements of forest structure and eddy‐covariance data of carbon and water fluxes over multiple decades across an environmental gradient at nine typical European forest stands. We test the models' performance in three dimensions: accuracy of local predictions (agreement of modelled and observed annual data), realism of environmental responses (agreement of modelled and observed responses of daily gross primary productivity to temperature, radiation and vapour pressure deficit) and general applicability (proportion of European tree species covered). We find that multiple models are available that excel according to our three dimensions of model performance. For the accuracy of local predictions, variables related to forest structure have lower random and systematic errors than annual carbon and water flux variables. Moreover, the multi‐model ensemble mean provided overall more realistic daily productivity responses to environmental drivers across all sites than any single individual model. The general applicability of the models is high, as almost all models are currently able to cover Europe's common tree species. We show that forest models complement each other in their response to environmental drivers and that there are several cases in which individual models outperform the model ensemble. Our framework provides a first step to capturing essential differences between forest models that go beyond the most commonly used accuracy of predictions. Overall, this study provides a point of reference for future model work aimed at predicting climate impacts and supporting climate mitigation and adaptation measures in forests.

Time Delta Head Impact Frequency: An Analysis on Head Impact Exposure in the Lead Up to a Concussion: Findings from the NCAA-DOD Care Consortium - Jack Seifert; Alok S. Shah; Jaroslaw Harezlak; Steven Rowson; Jason P. Mihalik; Larry Riggen; Stefan Duma; Alison Brooks; Kenneth L. Cameron; Christopher C. Giza; Joshua Goldman; Kevin M. Guskiewicz; et al. (Annals of Biomedical Engineering, 2022)
Sport-related concussions can result from a single high magnitude impact that generates concussive symptoms, repeated subconcussive head impacts aggregating to generate concussive symptoms, or a combined effect from the two mechanisms. The array of symptoms produced by these mechanisms may be clinically interpreted as a sport-related concussion. It was hypothesized that head impact exposure resulting in concussion is influenced by severity, total number, and frequency of subconcussive head impacts. The influence of total number and magnitude of impacts was previously explored, but frequency was investigated to a lesser degree. In this analysis, head impact frequency was investigated over a new metric called ‘time delta’, the time difference from the first recorded head impact of the day until the concussive impact. Four exposure metrics were analyzed over the time delta to determine whether frequency of head impact exposure was greater for athletes on their concussion date relative to other dates of contact participation. Those metrics included head impact frequency, head impact accrual rate, risk weighted exposure (RWE), and RWE accrual rate. Athletes experienced an elevated median number of impacts, RWE, and RWE accrual rate over the time delta on their concussion date compared to non-injury sessions. This finding suggests elevated frequency of head impact exposure on the concussion date compared to other dates that may precipitate the onset of concussion.

Population genomics of a predatory mammal reveals patterns of decline and impacts of exposure to toxic toads - Brenton von Takach; Louis Ranjard; Christopher P. Burridge; Skye F. Cameron; Teigan Cremona; Mark D. B. Eldridge; Diana O. Fisher; Stephen Frankenberg; Brydie M. Hill; Rosemary Hohnen; Chris J. Jolly; Ella Kelly; et al. (Molecular Ecology, 2022)
Mammal declines across northern Australia are one of the major biodiversity loss events occurring globally. There has been no regional assessment of the implications of these species declines for genomic diversity. To address this, we conducted a species‐wide assessment of genomic diversity in the northern quoll ( Dasyurus hallucatus ), an Endangered marsupial carnivore. We used next generation sequencing methods to genotype 10,191 single nucleotide polymorphisms (SNPs) in 352 individuals from across a 3220‐km length of the continent, investigating patterns of population genomic structure and diversity, and identifying loci showing signals of putative selection. We found strong heterogeneity in the distribution of genomic diversity across the continent, characterized by (i) biogeographical barriers driving hierarchical population structure through long‐term isolation, and (ii) severe reductions in diversity resulting from population declines, exacerbated by the spread of introduced toxic cane toads ( Rhinella marina ). These results warn of a large ongoing loss of genomic diversity and associated adaptive capacity as mammals decline across northern Australia. Encouragingly, populations of the northern quoll established on toad‐free islands by translocations appear to have maintained most of the initial genomic diversity after 16 years. By mapping patterns of genomic diversity within and among populations, and investigating these patterns in the context of population declines, we can provide conservation managers with data critical to informed decision‐making. This includes the identification of populations that are candidates for genetic management, the importance of remnant island and insurance/translocated populations for the conservation of genetic diversity, and the characterization of putative evolutionarily significant units.

Global patterns in endemicity and vulnerability of soil fungi - Leho Tedersoo; Vladimir Mikryukov; Alexander Zizka; Mohammad Bahram; Niloufar Hagh‐Doust; Sten Anslan; Oleh Prylutskyi; Manuel Delgado‐Baquerizo; Fernando T. Maestre; Jaan Pärn; Maarja Öpik; Mari Moora; et al. (Global Change Biology, 2022)
Fungi are highly diverse organisms, which provide multiple ecosystem services. However, compared with charismatic animals and plants, the distribution patterns and conservation needs of fungi have been little explored. Here, we examined endemicity patterns, global change vulnerability and conservation priority areas for functional groups of soil fungi based on six global surveys using a high‐resolution, long‐read metabarcoding approach. We found that the endemicity of all fungi and most functional groups peaks in tropical habitats, including Amazonia, Yucatan, West‐Central Africa, Sri Lanka, and New Caledonia, with a negligible island effect compared with plants and animals. We also found that fungi are predominantly vulnerable to drought, heat and land‐cover change, particularly in dry tropical regions with high human population density. Fungal conservation areas of highest priority include herbaceous wetlands, tropical forests, and woodlands. We stress that more attention should be focused on the conservation of fungi, especially root symbiotic arbuscular mycorrhizal and ectomycorrhizal fungi in tropical regions as well as unicellular early‐diverging groups and macrofungi in general. Given the low overlap between the endemicity of fungi and macroorganisms, but high conservation needs in both groups, detailed analyses on distribution and conservation requirements are warranted for other microorganisms and soil organisms.

Plant responses to soil biota depend on precipitation history, plant diversity, and productivity - Seth Lundell; Amgaa Batbaatar; Cameron N. Carlyle; Eric G. Lamb; Rafael Otfinowski; Michael P. Schellenberg; Jonathan A. Bennett (Ecology, 2022)
Soil biota are critical drivers of plant growth, population dynamics, and community structure and thus have wide‐ranging effects on ecosystem function. Interactions between plants and soil biota are complex, however, and can depend on the diversity and productivity of the plant community and environmental conditions. Plant–soil biota interactions may be especially important during stressful periods, such as drought, when plants can gain great benefits from beneficial biota but may be susceptible to antagonists. How soil biota respond to drought is also important and can influence plant growth following drought and leave legacies that affect future plant responses to soil biota and further drought. To explore how drought legacies and plant community context influence plant growth responses to soil biota and further drought, we collected soils from 12 grasslands varying in plant diversity and productivity where precipitation was experimentally reduced. We used these soils as inoculum in a growth chamber experiment testing how precipitation history (ambient or reduced) and soil biota (live or sterile soil inoculum) mediate plant growth and drought responses within an experimental plant community. We also tested whether these responses differed with the diversity and productivity of the community where the soil was collected. Plant growth responses to soil biota were positive when inoculated with soils from less diverse and productive plant communities and became negative as the diversity and productivity of the conditioning community increased. At low diversity, however, positive soil biota effects on plant growth were eliminated if precipitation had been reduced in the field, suggesting that diversity loss may heighten climate change sensitivity. Differences among species within the experimental community in their responses to soil biota and drought suggest that species benefitting from less drought sensitive soil biota may be able to compensate for some of this loss of productivity. Regardless of the plant species and soil origin, further drought eliminated any effects of soil biota on plant growth. Consequently, soil biota may be unable to buffer the effects of drought on primary productivity or other ecosystem functions as extreme events increase in frequency.

The S-Factor, a New Measure of Disease Severity in Spinocerebellar Ataxia: Findings and Implications - Louisa P. Selvadurai; Susan L. Perlman; George R. Wilmot; Sub H. Subramony; Christopher M. Gomez; Tetsuo Ashizawa; Henry L. Paulson; Chiadi U. Onyike; Liana S. Rosenthal; Haris I. Sair; Sheng-Han Kuo; Eva-Maria Ratai; et al. (The Cerebellum, 2022)

Impacts of Warming and Acidification on Coral Calcification Linked to Photosymbiont Loss and Deregulation of Calcifying Fluid pH - Louise P. Cameron; Claire E. Reymond; Jelle Bijma; Janina V. Büscher; Dirk De Beer; Maxence Guillermic; Robert A. Eagle; John Gunnell; Fiona Müller-Lundin; Gertraud M. Schmidt-Grieb; Isaac Westfield; Hildegard Westphal; et al. (Journal of Marine Science and Engineering, 2022)
Corals are globally important calcifiers that exhibit complex responses to anthropogenic warming and acidification. Although coral calcification is supported by high seawater pH, photosynthesis by the algal symbionts of zooxanthellate corals can be promoted by elevated pCO2. To investigate the mechanisms underlying corals’ complex responses to global change, three species of tropical zooxanthellate corals (Stylophora pistillata, Pocillopora damicornis, and Seriatopora hystrix) and one species of asymbiotic cold-water coral (Desmophyllum pertusum, syn. Lophelia pertusa) were cultured under a range of ocean acidification and warming scenarios. Under control temperatures, all tropical species exhibited increased calcification rates in response to increasing pCO2. However, the tropical species’ response to increasing pCO2 flattened when they lost symbionts (i.e., bleached) under the high-temperature treatments—suggesting that the loss of symbionts neutralized the benefit of increased pCO2 on calcification rate. Notably, the cold-water species that lacks symbionts exhibited a negative calcification response to increasing pCO2, although this negative response was partially ameliorated under elevated temperature. All four species elevated their calcifying fluid pH relative to seawater pH under all pCO2 treatments, and the magnitude of this offset (Δ[H+]) increased with increasing pCO2. Furthermore, calcifying fluid pH decreased along with symbiont abundance under thermal stress for the one species in which calcifying fluid pH was measured under both temperature treatments. This observation suggests a mechanistic link between photosymbiont loss (‘bleaching’) and impairment of zooxanthellate corals’ ability to elevate calcifying fluid pH in support of calcification under heat stress. This study supports the assertion that thermally induced loss of photosymbionts impairs tropical zooxanthellate corals’ ability to cope with CO2-induced ocean acidification.

Physicochemical Control of Caribbean Coral Calcification Linked to Host and Symbiont Responses to Varying pCO2 and Temperature - Robert A. Eagle; Maxence Guillermic; Illian De Corte; Blanca Alvarez Caraveo; Colleen B. Bove; Sambuddha Misra; Louise P. Cameron; Karl D. Castillo; Justin B. Ries (Journal of Marine Science and Engineering, 2022)
It is thought that the active physiological regulation of the chemistry of a parent fluid is an important process in the biomineralization of scleractinian corals. Biological regulation of calcification fluid pH (pHCF) and other carbonate chemistry parameters ([CO32−]CF, DICCF, and ΩCF) may be challenged by CO2 driven acidification and temperature. Here, we examine the combined influence of changing temperature and CO2 on calcifying fluid regulation in four common Caribbean coral species—Porites astreoides, Pseudodiploria strigosa, Undaria tenuifolia, and Siderastrea siderea. We utilize skeletal boron geochemistry (B/Ca and δ11B) to probe the pHCF, [CO32−]CF, and DICCF regulation in these corals, and δ13C to track changes in the sources of carbon for calcification. Temperature was found to not influence pHCF regulation across all pCO2 treatments in these corals, in contrast to recent studies on Indo-Pacific pocilloporid corals. We find that [DIC]CF is significantly lower at higher temperatures in all the corals, and that the higher temperature was associated with depletion of host energy reserves, suggesting [DIC]CF reductions may result from reduced input of respired CO2 to the DIC pool for calcification. In addition, δ13C data suggest that under high temperature and CO2 conditions, algal symbiont photosynthesis continues to influence the calcification pool and is associated with low [DIC]CF in P. strigosa and P. astreoides. In P. astreoides this effect is also associated with an increase in chlorophyll a concentration in coral tissues at higher temperatures. These observations collectively support the assertion that physicochemical control over coral calcifying fluid chemistry is coupled to host and symbiont physiological responses to environmental change, and reveals interspecific differences in the extent and nature of this coupling.

Targeting Sagebrush (Artemisia Spp.) Restoration Following Wildfire with Greater Sage-Grouse (Centrocercus Urophasianus) Nest Selection and Survival Models - Cali L. Roth; Shawn T. O’Neil; Peter S. Coates; Mark A. Ricca; David A. Pyke; Cameron L. Aldridge; Julie A. Heinrichs; Shawn P. Espinosa; David J. Delehanty (Environmental Management, 2022)
Unprecedented conservation efforts for sagebrush ( Artemisia spp.) ecosystems across the western United States have been catalyzed by risks from escalated wildfire activity that reduces habitat for sagebrush-obligate species such as Greater Sage-Grouse ( Centrocercus urophasianus ). However, post-fire restoration is challenged by spatial variation in ecosystem processes influencing resilience to disturbance and resistance to non-native invasive species, and spatial and temporal lags between slower sagebrush recovery processes and faster demographic responses of sage-grouse to loss of important habitat. Decision-support frameworks that account for these factors can help users strategically apply restoration efforts by predicting short and long-term ecological benefits of actions. Here, we developed a framework that strategically targets burned areas for restoration actions (e.g., seeding or planting sagebrush) that have the greatest potential to positively benefit sage-grouse populations through time. Specifically, we estimated sagebrush recovery following wildfire and risk of non-native annual grass invasion under four scenarios: passive recovery, grazing exclusion, active restoration with seeding, and active restoration with seedling transplants. We then applied spatial predictions of integrated nest site selection and survival models before wildfire, immediately following wildfire, and at 30 and 50 years post-wildfire based on each restoration scenario and measured changes in habitat. Application of this framework coupled with strategic planting designs aimed at developing patches of nesting habitat may help increase operational resilience for fire-impacted sagebrush ecosystems.

Traits and tradeoffs among non‐native ectomycorrhizal fungal symbionts affect pine seedling establishment in a Hawaiian coinvasion landscape - Leah Thompson; Sean O. I. Swift; Cameron P. Egan; Danyel Yogi; Thomas Chapin; Nicole A. Hynson (Molecular Ecology, 2022)
Pine invasions lead to losses of native biodiversity and ecosystem function, but pine invasion success is often linked to coinvading non‐native ectomycorrhizal (EM) fungi. How the community composition, traits, and distributions of these fungi vary over the landscape and how this affects pine success is understudied. A greenhouse bioassay experiment was performed to test the effects of changes in EM fungal community structure from a pine plantation, to an invasion front to currently pine‐free areas on percent root colonization and seedling biomass. Soils were also analysed by qPCR to determine changes in inoculum and spore density over distance for a common coinvading EM fungus, Suillus pungens . Percent colonization increased with distance from the plantation, which corresponded with an increase in seedling biomass and stark changes in EM fungal community membership where Suillus spp. dominated currently pine‐free areas. However, there was a negative relationship between S. pungens inoculum potential versus root colonization over distance. We conclude that the success of pine invasions is facilitated by specific traits of Suillus spp., but that the success of Suillus is contingent on a lack of competition with other ectomycorrhizal fungi.

Effects of elevated pCO 2 and temperature on the calcification rate, survival, extrapallial fluid chemistry, and respiration of the Atlantic Sea scallop Placopecten magellanicus - Louise P. Cameron; Jonathan H. Grabowski; Justin B. Ries (Limnology and Oceanography, 2022)
Anthropogenic CO 2 ‐emission is causing ocean warming and acidification. Understanding how basic physiological processes of marine organisms respond to these stressors is important for predicting their responses to future global change. We examined the effects of elevated pCO 2 and temperature (pCO 2 = 344–2199 ppm; temperature = 6°C, 9°C, and 12°C) on the calcification rate, extrapallial fluid (EPF) carbonate chemistry, respiration, and survivorship of Atlantic sea scallops ( Placopecten magellanicus ) in a fully crossed 143‐d experiment. Rates of calcification and respiration were inhibited by elevated pCO 2 , and mortality occurred when elevated pCO 2 was accompanied by high‐temperature stress. Declines in growth and survivorship were likely caused by external shell dissolution, thermal stress, and hypercapnic reduction of metabolism under elevated pCO 2 . Concentrations of dissolved inorganic carbon (DIC) and total alkalinity in the EPF increased above seawater concentrations in response to elevated pCO 2 . EPF pH declined, but did not decline as much as seawater pH, indicating that scallops regulate EPF pH to support calcification. The combination of EPF pH regulation and DIC elevation yielded an increase in EPF [] under elevated pCO 2 treatments. The combination of low respiration rates, high EPF [], and low calcification rates under elevated pCO 2 suggests that the impaired calcification arises more from hypercapnic inhibition of metabolic activity and external shell dissolution than from chemically unfavorable conditions in the EPF. These results demonstrate the importance of EPF chemistry for bivalve biomineralization, but show that regulation efforts are insufficient to fully offset the deleterious effects of elevated pCO 2 on scallop performance.

Improving sightings-derived residency estimation for whale shark aggregations: A novel metric applied to a global data set - Gonzalo Araujo; Ariana Agustines; Steffen S. Bach; Jesse E. M. Cochran; Emilio de la Parra-Galván; Rafael de la Parra-Venegas; Stella Diamant; Alistair Dove; Steve Fox; Rachel T. Graham; Sofia M. Green; Jonathan R. Green; et al. (Frontiers in Marine Science, 2022)
The world’s largest extant fish, the whale shark Rhincodon typus , is one of the most-studied species of sharks globally. The discovery of predictable aggregation sites where these animals gather seasonally or are sighted year-round – most of which are coastal and juvenile-dominated – has allowed for a rapid expansion of research on this species. The most common method for studying whale sharks at these sites is photographic identification (photo-ID). This technique allows for long-term individual-based data to be collected which can, in turn, be used to evaluate population structure, build population models, identify long-distance movements, and assess philopatry and other population dynamics. Lagged identification rate (LIR) models have fewer underlying assumptions than more traditional capture mark recapture approaches, making them more broadly applicable to marine taxa, especially far-ranging megafauna species like whale sharks. However, the increased flexibility comes at a cost. Parameter estimations based on LIR can be difficult to interpret and may not be comparable between areas with different sampling regimes. Using a unique data-set from the Philippines with ~8 years of nearly continuous survey effort, we were able to derive a metric for converting LIR residency estimates into more intuitive days-per-year units. We applied this metric to 25 different sites allowing for the first quantitatively-meaningful comparison of sightings-derived residence among the world’s whale shark aggregations. We validated these results against the only three published acoustic residence metrics (falling within the ranges established by these earlier works in all cases). The results were then used to understand residency behaviours exhibited by the sharks at each site. The adjusted residency metric is an improvement to LIR-based population modelling, already one of the most widely used tools for describing whale shark aggregations. The standardised methods presented here can serve as a valuable tool for assessing residency patterns of whale sharks, which is crucial for tailored conservation action, and can cautiously be tested in other taxa.

Delineation of blacktip shark ( Carcharhinus limbatus ) nursery habitats in the north‐western Gulf of Mexico - Philip Matich; Camryn L. Bigelow; Barrett Chambers; Jillian J. Dodds; Jessica A. Hebert; Alexis Lemieux; Christy M. Pittman; Julianna Trapp; Brooke Bianco; Carolina P. Cadena; Emily I. Castillo; Gabriela I. Castillo; et al. (Journal of Fish Biology, 2022)
Coevolution with predators leads to the use of low‐risk habitats by many prey species, which promotes survival during early developmental phases. These nurseries are valued by conservation and management agencies because of their contributions to adult populations. However, the physical and geographic characteristics, like shallow depths and isolation from other marine habitats, that restrict access to predators and thereby reduce risk to juvenile animals can also limit scientific research. Consequently, many nursery habitats are still unidentified and understudied. Here we used gillnet monitoring from 1982 to 2018 to delineate blacktip shark ( Carcharhinus limbatus ) nurseries in the north‐western Gulf of Mexico and elucidated their physical, environmental and biological characteristics. Nursery habitats within estuaries (

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Estimated life-history traits and movements of the Caribbean reef shark (Carcharhinus perezi) in The Bahamas based on tag-recapture data - Brendan S. Talwar; Darcy Bradley; Christopher Berry; Mark E. Bond; Ian A. Bouyoucos; Annabelle M. L. Brooks; Candace Y. A. Fields; Austin J. Gallagher; Tristan L. Guttridge; Annie E. Guttridge; Neil Hammerschlag; Ian Hamilton; et al. (Marine Biology, 2022)

Two common bee-sampling methods reflect different assemblages of the bee (Hymenoptera: Apoidea) community in mixed-grass prairie systems and are dependent on surrounding floral resource availability - C. K. Pei; Torre J. Hovick; Cameron A. Duquette; Ryan F. Limb; Jason P. Harmon; Benjamin A. Geaumont (Journal of Insect Conservation, 2022)

The impact of weather on the incidence of dark cutting in Australian feedlot cattle - Cameron Steel; A. M. Lees; G. Tarr; R. Warner; F. Dunshea; F. Cowley; P. McGilchrist (International Journal of Biometeorology, 2022)

Adaptive divergence in bill morphology and other thermoregulatory traits is facilitated by restricted gene flow in song sparrows on the California Channel Islands - Maybellene P. Gamboa; Cameron K. Ghalambor; T. Scott Sillett; Scott A. Morrison; W. Chris Funk (Molecular Ecology, 2022)
Disentangling the effects of neutral and adaptive processes in maintaining phenotypic variation across environmental gradients is challenging in natural populations. Song sparrows ( Melospiza melodia ) on the California Channel Islands occupy a pronounced east‐west climate gradient within a small spatial scale, providing a unique opportunity to examine the interaction of genetic isolation (reduced gene flow) and the environment (selection) in driving variation. We used reduced representation genomic libraries to infer the role of neutral processes (drift and restricted gene flow) and divergent selection in driving variation in thermoregulatory traits with an emphasis on the mechanisms that maintain bill divergence among islands. Analyses of 22,029 neutral SNPs confirm distinct population structure by island with restricted gene flow and relatively large effective population sizes, suggesting bill differences are probably not a product of genetic drift. Instead, we found strong support for local adaptation using 3294 SNPs in differentiation‐based and environmental association analyses coupled with genome‐wide association tests. Specifically, we identified several putatively adaptive and candidate loci in or near genes involved in bill development pathways (e.g., BMP , CaM , Wnt ), confirming the highly complex and polygenic architecture underlying bill morphology. Furthermore, we found divergence in genes associated with other thermoregulatory traits (i.e., feather structure, plumage colour, and physiology). Collectively, these results suggest strong divergent selection across an island archipelago results in genomic changes in a suite of traits associated with climate adaptation over small spatial scales. Future research should move beyond studying univariate traits to better understand multidimensional responses to complex environmental conditions.

Elemental Metabolomics for Prediction of Term Gestational Outcomes Utilising 18-Week Maternal Plasma and Urine Samples - Daniel R. McKeating; Vicki L. Clifton; Cameron P. Hurst; Joshua J. Fisher; William W. Bennett; Anthony V. Perkins (Biological Trace Element Research, 2021)

Ocean Acidification Induces Subtle Shifts in Gene Expression and DNA Methylation in Mantle Tissue of the Eastern Oyster (Crassostrea virginica) - Alan M. Downey-Wall; Louise P. Cameron; Brett M. Ford; Elise M. McNally; Yaamini R. Venkataraman; Steven B. Roberts; Justin B. Ries; Katie E. Lotterhos (Frontiers in Marine Science, 2020)

Noradrenergic circuits in the forebrain control affective responses to novelty - Daniel Lustberg; Rachel P. Tillage; Yu Bai; Molly Pruitt; L. Cameron Liles; David Weinshenker (Psychopharmacology, 2020)

Concussion Risk Between Individual Football Players: Survival Analysis of Recurrent Events and Non-events - Steven Rowson; Eamon T. Campolettano; Stefan M. Duma; Brian Stemper; Alok Shah; Jaroslaw Harezlak; Larry Riggen; Jason P. Mihalik; Alison Brooks; Kenneth L. Cameron; Steven J. Svoboda; Megan N. Houston; et al. (Annals of Biomedical Engineering, 2020)

High Energy Side and Rear American Football Head Impacts Cause Obvious Performance Decrement on Video - Adam J. Bartsch; Daniel Hedin; Jay Alberts; Edward C. Benzel; Jason Cruickshank; Robert S. Gray; Kenneth Cameron; Megan N. Houston; Tyler Rooks; Gerald McGinty; Erick Kozlowski; Steven Rowson; et al. (Annals of Biomedical Engineering, 2020)

Three decades post‐reforestation has not led to the reassembly of arbuscular mycorrhizal fungal communities associated with remnant primary forests - Christopher B. Wall; Cameron P. Egan; Sean I. O. Swift; Nicole A. Hynson (Molecular Ecology, 2020)
The negative effects of deforestation can potentially be ameliorated through ecological restoration. However, reforestation alone may not reassemble the same ecological communities or functions as primary forests. In part, this failure may be owed to forest ecosystems inherently involving complex interactions among guilds of organisms. Plants, which structure forest food webs, rely on intimate associations with symbiotic microbes such as root‐inhabiting mycorrhizal fungi. Here, we leverage a large‐scale reforestation project on Hawai‘i Island underway for over three decades to assess whether arbuscular mycorrhizal (AM) fungal communities have concurrently been restored. The reference ecosystem for this restoration project is a remnant montane native Hawaiian forest that provides critical habitat for endangered birds. We sampled soils from 12 plots within remnant and restored forest patches and characterized AM fungal communities using high‐throughput amplicon sequencing. While some AM fungal community metrics were comparable between remnant and restored forest (e.g. species richness), other key characteristics were not. Specifically, community membership and the identity of AM fungal keystone species differed between the two habitat types, as well as the primary environmental factors influencing community composition. Remnant forest AM fungal communities were strongly associated with soil chemical properties, especially pH, while restored forest communities were influenced by the spatial proximity to remnant forests. We posit that combined, these differences in soil AM fungal communities could be negatively affecting the recruitment of native plant hosts and that future restoration efforts should consider plant–microbe interactions as an important facet of forest health.

Central norepinephrine transmission is required for stress-induced repetitive behavior in two rodent models of obsessive-compulsive disorder - Daniel Lustberg; Alexa F. Iannitelli; Rachel P. Tillage; Molly Pruitt; L. Cameron Liles; David Weinshenker (Psychopharmacology, 2020)

Introgressing blue mold resistance into elite apple germplasm by rapid cycle breeding and foreground and background DNA-informed selection - Feixiong Luo; John L. Norelli; Nicholas P. Howard; Michael Wisniewski; Henryk Flachowsky; Magda-Viola Hanke; Cameron Peace (Tree Genetics & Genomes, 2020)

Risks and benefits of pasture irrigation using treated municipal effluent : a lysimeter case study, Canterbury, New Zealand - Maria Jesus Gutierrez-Gines; Minakshi Mishra; Cameron McIntyre; Henry Wai Chau; Juergen Esperschuetz; Roger McLenaghen; Mike P. Bourke; Brett H. Robinson (Environmental Science and Pollution Research, 2020)
Compared to discharge into waterways, land application of treated municipal effluent (TME) can reduce the need for both inorganic fertilizers and irrigation. However, TME irrigation may result in the accumulation of phosphorus (P) or trace elements in soil, and increased salinity and sodicity, which could damage soil structure and reduce infiltration. TME irrigation can also result in groundwater contamination through nitrate leaching or surface water contamination through runoff. This study aimed to evaluate the effects of increasing TME irrigation rates on quantity and quality of leachate and pasture growth in a lysimeter experiment using a Fluvial Recent soil and a Fragic Pallic soil. Pasture growth in the lysimeters was up to 2.5-fold higher in the TME treatments compared to the non-irrigated treatments. There were no signs of toxicity or accumulation of B, Al, Cd, Cu, Fe, Mn, As, and Zn. TME significantly increased the concentration of P and Na in the pasture. Nitrogen leaching from the lysimeters was negligible (< 1 kg/ha −1 equiv.) in all treatments, but mineral N accumulated in the soil profile of the highest application rate (1672 mm/yr). Although more P was added than removed in pasture, the rate of accumulation indicated that over a 50-year period, P will still be within the current New Zealand thresholds for grazed pastures. Sodium accumulated in the soil columns in all the TME treatments. The rate of accumulation was not proportional to the TME application rate, indicating that Na was moving down through the soil profile and leaching. Results indicate a low to moderate risk of sodicity in soil or toxicity in plants caused by Na.

Elimination of galanin synthesis in noradrenergic neurons reduces galanin in select brain areas and promotes active coping behaviors - Rachel P. Tillage; Natale R. Sciolino; Nicholas W. Plummer; Daniel Lustberg; L. Cameron Liles; Madeline Hsiang; Jeanne M. Powell; Kathleen G. Smith; Patricia Jensen; David Weinshenker (Brain Structure and Function, 2020)

Repetitive Head Impact Exposure in College Football Following an NCAA Rule Change to Eliminate Two-A-Day Preseason Practices: A Study from the NCAA-DoD CARE Consortium - Brian D. Stemper; Alok S. Shah; Jaroslaw Harezlak; Steven Rowson; Stefan Duma; Jason P. Mihalik; Larry D. Riggen; Alison Brooks; Kenneth L. Cameron; Christopher C. Giza; Megan N. Houston; Jonathan Jackson; et al. (Annals of Biomedical Engineering, 2019)

Accounting for Variance in Concussion Tolerance Between Individuals: Comparing Head Accelerations Between Concussed and Physically Matched Control Subjects - Steven Rowson; Eamon T. Campolettano; Stefan M. Duma; Brian Stemper; Alok Shah; Jaroslaw Harezlak; Larry Riggen; Jason P. Mihalik; Kevin M. Guskiewicz; Christopher Giza; Alison Brooks; Kenneth Cameron; et al. (Annals of Biomedical Engineering, 2019)

Factors Affecting Head Impact Exposure in College Football Practices: A Multi-Institutional Study - Eamon T. Campolettano; Steven Rowson; Stefan M. Duma; Brian Stemper; Alok Shah; Jaroslaw Harezlak; Larry D. Riggen; Jason Mihalik; Alison Brooks; Kenneth Cameron; Christoper C. Giza; Thomas McAllister; et al. (Annals of Biomedical Engineering, 2019)

Comparison of Head Impact Exposure Between Concussed Football Athletes and Matched Controls: Evidence for a Possible Second Mechanism of Sport-Related Concussion - Brian D. Stemper; Alok S. Shah; Jaroslaw Harezlak; Steven Rowson; Jason P. Mihalik; Stefan M. Duma; Larry D. Riggen; Alison Brooks; Kenneth L. Cameron; Darren Campbell; John P. DiFiori; Christopher C. Giza; et al. (Annals of Biomedical Engineering, 2019)

Global mismatches in aboveground and belowground biodiversity - Erin K. Cameron; Inês S. Martins; Patrick Lavelle; Jérôme Mathieu; Leho Tedersoo; Mohammad Bahram; Felix Gottschall; Carlos A. Guerra; Jes Hines; Guillaume Patoine; Julia Siebert; Marten Winter; et al. (Conservation Biology, 2019)
Human activities are accelerating global biodiversity change and have resulted in severely threatened ecosystem services. A large proportion of terrestrial biodiversity is harbored by soil, but soil biodiversity has been omitted from many global biodiversity assessments and conservation actions, and understanding of global patterns of soil biodiversity remains limited. In particular, the extent to which hotspots and coldspots of aboveground and soil biodiversity overlap is not clear. We examined global patterns of these overlaps by mapping indices of aboveground (mammals, birds, amphibians, vascular plants) and soil (bacteria, fungi, macrofauna) biodiversity that we created using previously published data on species richness. Areas of mismatch between aboveground and soil biodiversity covered 27% of Earth's terrestrial surface. The temperate broadleaf and mixed forests biome had the highest proportion of grid cells with high aboveground biodiversity but low soil biodiversity, whereas the boreal and tundra biomes had intermediate soil biodiversity but low aboveground biodiversity. While more data on soil biodiversity are needed, both to cover geographic gaps and to include additional taxa, our results suggest that protecting aboveground biodiversity may not sufficiently reduce threats to soil biodiversity. Given the functional importance of soil biodiversity and the role of soils in human well‐being, soil biodiversity should be considered further in policy agendas and conservation actions by adapting management practices to sustain soil biodiversity and considering soil biodiversity when designing protected areas.

Neural entrainment is associated with subjective groove and complexity for performed but not mechanical musical rhythms - Daniel J. Cameron; Ioanna Zioga; Job P. Lindsen; Marcus T. Pearce; Geraint A. Wiggins; Keith Potter; Joydeep Bhattacharya (Experimental Brain Research, 2019)

Simulating the Antarctic stratospheric vortex transport barrier: comparing the Unified Model to reanalysis - Chris Cameron; Gregory E. Bodeker; Jonathan P. Conway; Stephen Stuart; James Renwick (Climate Dynamics, 2019)

Aversion learning in response to an invasive venomous prey depends on stimulus strength - Cameron P. Venable; Thomas S. Adams; Tracy Langkilde (Biological Invasions, 2019)

Characterizing range-wide divergence in an alpine-endemic bird: a comparison of genetic and genomic approaches - Kathryn M. Langin; Cameron L. Aldridge; Jennifer A. Fike; R. Scott Cornman; Kathy Martin; Gregory T. Wann; Amy E. Seglund; Michael A. Schroeder; Clait E. Braun; David P. Benson; Brad C. Fedy; Jessica R. Young; et al. (Conservation Genetics, 2018)

Does sowing an oats catch crop reduce nitrate leaching from urine deposition following simulated winter forage grazing? - a growth chamber experiment - P. L. Carey; K. C. Cameron; H. J. Di; G. R. Edwards (Plant and Soil, 2018)

Comparative metabolomic responses to gibberellic acid and 6-benzylaminopurine in Cunila menthoides Benth. (Lamiaceae): a contribution to understand the metabolic pathways - Joana P. S. Oliveira; Maria Gabriela B. Koblitz; Mariana S. L. Ferreira; L. C. Cameron; Andrea F. Macedo (Plant Cell Reports, 2018)

Tissue culture and metabolome investigation of a wild endangered medicinal plant using high definition mass spectrometry - J. P. S. Oliveira; O. Hakimi; M. Murgu; M. G. B. Koblitz; M. S. L. Ferreira; L. C. Cameron; A. F. Macedo (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Long-term grazing impacts on vegetation diversity, composition, and exotic species presence across an aridity gradient in northern temperate grasslands - Mark P. Lyseng; Edward W. Bork; Daniel B. Hewins; Mike J. Alexander; Cameron N. Carlyle; Scott X. Chang; Walter D. Willms (Plant Ecology, 2018)

The putative leucine sensor Sestrin2 is hyperphosphorylated by acute resistance exercise but not protein ingestion in human skeletal muscle - Nina Zeng; Randall F. D’Souza; Brie Sorrenson; Troy L. Merry; Matthew P. G. Barnett; Cameron J. Mitchell; David Cameron-Smith (European Journal of Applied Physiology, 2018)

Fluorescence Correlation Spectroscopy with Photobleaching Correction in Slowly Diffusing Systems - Cameron Hodges; Rudra P. Kafle; J. Damon Hoff; Jens-Christian Meiners (Journal of Fluorescence, 2018)

Erratum to: Modelling foetal exposure to maternal smoking using hepatoblasts from pluripotent stem cells - Baltasar Lucendo-Villarin; Panagiotis Filis; Madeleine J. Swortwood; Marilyn A. Huestis; Jose Meseguer-Ripolles; Kate Cameron; John P. Iredale; Peter J. O’Shaughnessy; Paul A. Fowler; David C. Hay (Archives of Toxicology, 2017)

Modelling foetal exposure to maternal smoking using hepatoblasts from pluripotent stem cells - Baltasar Lucendo-Villarin; Panagiotis Filis; Madeleine J. Swortwood; Marilyn A. Huestis; Jose Meseguer-Ripolles; Kate Cameron; John P. Iredale; Peter J. O’Shaughnessy; Paul A. Fowler; David C. Hay (Archives of Toxicology, 2017)

Evolutionary shifts in anti-predator responses of invasive cane toads (Rhinella marina) - Cameron M. Hudson; Gregory P. Brown; Richard Shine (Behavioral Ecology and Sociobiology, 2017)

Quantifying the extent of niche areas in the global fleet of commercial ships: the potential for “super-hot spots” of biofouling - Cameron S. Moser; Timothy P. Wier; Matthew R. First; Jonathan F. Grant; Scott C. Riley; Stephanie H. Robbins-Wamsley; Mario N. Tamburri; Gregory M. Ruiz; A. Whitman Miller; Lisa A. Drake (Biological Invasions, 2017)

Interspecific hybridization causes long‐term phylogenetic discordance between nuclear and mitochondrial genomes in freshwater fishes - Graham P. Wallis; Sophia R. Cameron‐Christie; Hannah L. Kennedy; Gemma Palmer; Tessa R. Sanders; David J. Winter (Molecular Ecology, 2017)
Classification, phylogeography and the testing of evolutionary hypotheses rely on correct estimation of species phylogeny. Early molecular phylogenies often relied on mt DNA alone, which acts as a single linkage group with one history. Over the last decade, the use of multiple nuclear sequences has often revealed conflict among gene trees. This observation can be attributed to hybridization, lineage sorting, paralogy or selection. Here, we use 54 groups of fishes from 48 studies to estimate the degree of concordance between mitochondrial and nuclear gene trees in two ecological grades of fishes: marine and freshwater. We test the hypothesis that freshwater fish phylogenies should, on average, show more discordance because of their higher propensity for hybridization in the past. In keeping with this idea, concordance between mitochondrial and nuclear gene trees (as measured by proportion of components shared) is on average 50% higher in marine fishes. We discuss why this difference almost certainly results from introgression caused by greater historical hybridization among lineages in freshwater groups, and further emphasize the need to use multiple nuclear genes, and identify conflict among them, in estimation of species phylogeny.

Sublethal effects of angling and release on golden perch Macquaria ambigua : implications for reproduction and fish health - K. C. Hall; M. K. Broadhurst; P. A. Butcher; L. Cameron; S. J. Rowland; R. B. Millar (Journal of Fish Biology, 2017)
The present study tested the hypothesis of no delayed sublethal effects of mild angling and release on the feeding, growth, somatic condition and gonadal development of golden perch Macquaria ambigua during gametogenesis. Subsamples of adult M. ambigua ( n = 17–21 of 207), originally captured from the wild and stocked into ten 0·1 ha earthen ponds, were angled and released during early and late gametogenesis. Wild samples that were concurrently collected throughout the experiment underwent rapid and synchronous gonadal development and many spawned. While no spawning occurred in the ponds, most M. ambigua underwent normal gonadal development to maturity, including the angled fish. Angled fish also fed, maintained condition and actually grew faster than non‐angled captive controls. Although females that were angled during late gametogenesis more readily ingested and retained baited hooks, neither their subsequent condition nor gonadal development was significantly affected. The predominance of null results was attributed to the combined effects of the flexible reproductive strategy of M. ambigua , the benignness of mouth hooking and immediate release, and possible methodological issues arising from differential hooking success of more aggressive and resilient individuals. The findings support earlier catch‐and‐release research, but contrast with reports of acute reproductive effects following capture and handling for aquaculture broodstock. This discrepancy highlights the need for research to specifically address welfare questions relevant to recreational fisheries across various species and angling scenarios.

Phylogenetic structure of arbuscular mycorrhizal fungal communities along an elevation gradient - Cameron P. Egan; Ragan M. Callaway; Miranda M. Hart; Jason Pither; John Klironomos (Mycorrhiza, 2017)

The unseen invaders: introduced earthworms as drivers of change in plant communities in North American forests (a meta‐analysis) - Dylan Craven; Madhav P. Thakur; Erin K. Cameron; Lee E. Frelich; Robin Beauséjour; Robert B. Blair; Bernd Blossey; James Burtis; Amy Choi; Andrea Dávalos; Timothy J. Fahey; Nicholas A. Fisichelli; et al. (Global Change Biology, 2017)
Globally, biological invasions can have strong impacts on biodiversity as well as ecosystem functioning. While less conspicuous than introduced aboveground organisms, introduced belowground organisms may have similarly strong effects. Here, we synthesize for the first time the impacts of introduced earthworms on plant diversity and community composition in North American forests. We conducted a meta‐analysis using a total of 645 observations to quantify mean effect sizes of associations between introduced earthworm communities and plant diversity, cover of plant functional groups, and cover of native and non‐native plants. We found that plant diversity significantly declined with increasing richness of introduced earthworm ecological groups. While plant species richness or evenness did not change with earthworm invasion, our results indicate clear changes in plant community composition: cover of graminoids and non‐native plant species significantly increased, and cover of native plant species (of all functional groups) tended to decrease, with increasing earthworm biomass. Overall, these findings support the hypothesis that introduced earthworms facilitate particular plant species adapted to the abiotic conditions of earthworm‐invaded forests. Further, our study provides evidence that introduced earthworms are associated with declines in plant diversity in North American forests. Changing plant functional composition in these forests may have long‐lasting effects on ecosystem functioning.

Natural hazards in Australia: droughts - Anthony S. Kiem; Fiona Johnson; Seth Westra; Albert van Dijk; Jason P. Evans; Alison O’Donnell; Alexandra Rouillard; Cameron Barr; Jonathan Tyler; Mark Thyer; Doerte Jakob; Fitsum Woldemeskel; et al. (Climatic Change, 2016)

Orchid historical biogeography, diversification, Antarctica and the paradox of orchid dispersal - Thomas J. Givnish; Daniel Spalink; Mercedes Ames; Stephanie P. Lyon; Steven J. Hunter; Alejandro Zuluaga; Alfonso Doucette; Giovanny Giraldo Caro; James McDaniel; Mark A. Clements; Mary T. K. Arroyo; Lorena Endara; et al. (Journal of Biogeography, 2016)
Aim Orchidaceae is the most species‐rich angiosperm family and has one of the broadest distributions. Until now, the lack of a well‐resolved phylogeny has prevented analyses of orchid historical biogeography. In this study, we use such a phylogeny to estimate the geographical spread of orchids, evaluate the importance of different regions in their diversification and assess the role of long‐distance dispersal ( LDD ) in generating orchid diversity. Location Global. Methods Analyses use a phylogeny including species representing all five orchid subfamilies and almost all tribes and subtribes, calibrated against 17 angiosperm fossils. We estimated historical biogeography and assessed the importance of different regions for rates of speciation, extinction and net species diversification. We evaluated the impact of particular LDD events on orchid diversity by asking how many species evolved in the new range subsequent to those events. Results Orchids appear to have arisen in Australia 112 Ma (95% higher probability distribution: 102.0–120.0 Ma), then spread to the Neotropics via Antarctica by 90 Ma ( HPD : 79.7–99.5 Ma), when all three continents were in close contact and apostasioids split from the ancestor of all other orchids. Ancestors of vanilloids, cypripedioids and orchidoids+epidendroids appear to have originated in the Neotropics 84–64 Ma. Repeated long‐ and short‐distance dispersal occurred through orchid history: stochastic mapping identified a mean total of 74 LDD events or 0.8 Ma −1 . Across orchid history, Southeast Asia was the most important source and maximally accelerated net diversification; across epidendroids, the Neotropics maximally accelerated diversification. Main conclusions Our analysis provides the first biogeographical history of the orchids, implicating Australia, the Neotropics and Antarctica in their origin. LDD and life in the Neotropics – especially the Andes – had profound effects on their spread and diversification; > 97% of all orchid species are restricted to individual continents.

Mapping adipose and muscle tissue expression quantitative trait loci in African Americans to identify genes for type 2 diabetes and obesity - Satria P. Sajuthi; Neeraj K. Sharma; Jeff W. Chou; Nicholette D. Palmer; David R. McWilliams; John Beal; Mary E. Comeau; Lijun Ma; Jorge Calles-Escandon; Jamehl Demons; Samantha Rogers; Kristina Cherry; et al. (Human Genetics, 2016)

Dactylogyrus olfactorius n. sp. (Monogenea, Dactylogyridae) from the olfactory chamber of the fathead minnow, Pimephales promelas Rafinesque (Cyprinidae) - Ebrahim Lari; Rachael V. Adams; David K. Cone; Cameron P. Goater; Greg G. Pyle (Systematic Parasitology, 2016)

QTL mapping and breeding value estimation through pedigree-based analysis of fruit size and weight in four diverse peach breeding programs - Jonathan Fresnedo-Ramírez; Terrence J. Frett; Paul J. Sandefur; Alejandra Salgado-Rojas; John R. Clark; Ksenija Gasic; Cameron P. Peace; Natalie Anderson; Timothy P. Hartmann; David H. Byrne; Marco C. A. M. Bink; Eric van de Weg; et al. (Tree Genetics & Genomes, 2016)

Quantifying the total wetted surface area of the world fleet: a first step in determining the potential extent of ships’ biofouling - Cameron S. Moser; Timothy P. Wier; Jonathan F. Grant; Matthew R. First; Mario N. Tamburri; Gregory M. Ruiz; A. Whitman Miller; Lisa A. Drake (Biological Invasions, 2016)

Identification of novel Bromus- and Trifolium-associated circular DNA viruses - Simona Kraberger; Kata Farkas; Pauline Bernardo; Cameron Booker; Gerardo R. Argüello-Astorga; François Mesléard; Darren P. Martin; Philippe Roumagnac; Arvind Varsani (Archives of Virology, 2015)

A reconstruction of extratropical Indo-Pacific sea-level pressure patterns during the Medieval Climate Anomaly - Ian D. Goodwin; Stuart Browning; Andrew M. Lorrey; Paul A. Mayewski; Steven J. Phipps; Nancy A. N. Bertler; Ross P. Edwards; Tim J. Cohen; Tas van Ommen; Mark Curran; Cameron Barr; J. Curt Stager (Climate Dynamics, 2014)

Large multiethnic Candidate Gene Study for C-reactive protein levels: identification of a novel association at CD36 in African Americans - Jaclyn Ellis; Ethan M. Lange; Jin Li; Josee Dupuis; Jens Baumert; Jeremy D. Walston; Brendan J. Keating; Peter Durda; Ervin R. Fox; Cameron D. Palmer; Yan A. Meng; Taylor Young; et al. (Human Genetics, 2014)

THE BIOLOGY OF SHARKS AND RAYS ‐ By A. P. Klimley - Robert J. Bourdon; Mauricio Carrasquilla‐Henao; Brenna Collicutt; Cameron Freshwater; Olivia McMillan; Amber Messmer; James P. W. Robinson; Easton R. White; Francis Juanes (Journal of Fish Biology, 2014)

TLR4, IL10RA, and NOD2 mutation in paediatric Crohn’s disease patients: an association with Mycobacterium avium subspecies paratuberculosis and TLR4 and IL10RA expression - Josef Wagner; Narelle A. Skinner; Anthony G. Catto-Smith; Donald J. S. Cameron; Wojtek P. Michalski; Kumar Visvanathan; Carl D. Kirkwood (Medical Microbiology and Immunology, 2013)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

Yield and Woody Biomass Traits of Novel Shrub Willow Hybrids at Two Contrasting Sites - Michelle J. Serapiglia; Kimberly D. Cameron; Arthur J. Stipanovic; Lawrence P. Abrahamson; Timothy A. Volk; Lawrence B. Smart (BioEnergy Research, 2013)

Scientific Communication for Natural Resource Professionals Edited by Cecil A.Jennings, Thomas E.Lauer and BruceVondracek, American Fisheries Society, Bethesda, Maryland, USA, 2012, ISBN: 978‐1‐934874‐28‐8, Paperback USD 35.00, no UK price. Graphs and figures, 180 pp. - Cameron Freshwater; James P W Robinson; Cayla Naumann; Eric Hertz; David Stormer; Amy K Teffer; Francis Juanes (Fish and Fisheries, 2013)

A bivariate mixed model approach for the analysis of plant survival data - Aanandini Ganesalingam; Alison B. Smith; Cameron P. Beeck; Wallace A. Cowling; Robin Thompson; Brian R. Cullis (Euphytica, 2013)

Carbachol-Induced Volume Adaptation in Mouse Bladder and Length Adaptation via Rhythmic Contraction in Rabbit Detrusor - John E. Speich; Cameron W. Wilson; Atheer M. Almasri; Jordan B. Southern; Adam P. Klausner; Paul H. Ratz (Annals of Biomedical Engineering, 2012)

Fire persistence traits can be used to predict vegetation response to changing fire regimes at expansive landscape scales – an Australian example - Jeremy Russell‐Smith; Mark R. Gardener; Chris Brock; Kym Brennan; Cameron P. Yates; Blair Grace (Journal of Biogeography, 2012)
Aim Building on a substantial literature addressing the fire responses of woody plants, particularly under mediterranean climates, we assess the extent to which fire persistence traits can be used to predict vegetation responses to fire regime changes in fire‐prone arid and savanna landscape settings. Location Australia, applying data from arid central to monsoonal northern regions (11–26° S, 129–138° E). Methods With reference to a substantial sub‐continental floristics dataset, we first assigned the fire response (obligate seeder, resprouter) and seedbank persistence (transient, dormant) of rapid and longer‐maturing (> 3 years) woody taxa. Using logistic regression, we then modelled the proportions of taxa possessing these traits as a function of mean annual rainfall (highly correlated with fire frequency) and terrain roughness (a measure of topographic variability) in 0.25° × 0.25° and 1° × 1° grid cells. Separate assessments were undertaken with datasets for 1264 sclerophyll and 236 rain forest taxa. Results This woody flora is characterized by taxa exhibiting mostly resprouting and dormant seedbank traits that promote site persistence. While numbers of obligate seeder and resprouter taxa were related positively to both rainfall and roughness, the relative abundance of both sclerophyll and rain forest obligate seeders decreased significantly with rainfall. The relative abundance of sclerophyll (especially long‐lived) obligate seeders alone increased with topographic roughness. The proportion of taxa with transient seedbanks increased with rainfall in resprouters generally, and in rain forest obligate seeders alone. Main conclusions We find that resprouters are favoured on more productive, fire‐prone sites, and obligate seeders are favoured in less productive, more fire‐protected settings. Seedbank persistence responses are more variable. These findings concur generally with theoretical constructs, and support comparable assessments in Australian and other fire‐prone systems ranging from mediterranean to boreal environments. Our observations illustrate that resprouting and obligate seeding syndromes, but not necessarily seedbank persistence, are useful predictors of vegetation responses to changing fire regime conditions at large landscape scales.

The spatial range of contour integration deficits in schizophrenia - Brian P. Keane; Steven M. Silverstein; Deanna M. Barch; Cameron S. Carter; James M. Gold; Ilona Kovács; Angus W. MacDonald; J. Daniel Ragland; Milton E. Strauss (Experimental Brain Research, 2012)

Development of a Finite Element Model for Blast Brain Injury and the Effects of CSF Cavitation - Matthew B. Panzer; Barry S. Myers; Bruce P. Capehart; Cameron R. Bass (Annals of Biomedical Engineering, 2012)

Conservation in a cup of water: estimating biodiversity and population abundance from environmental DNA - DAVID M. LODGE; CAMERON R. TURNER; CHRISTOPHER L. JERDE; MATTHEW A. BARNES; LINDSAY CHADDERTON; SCOTT P. EGAN; JEFFREY L. FEDER; ANDREW R. MAHON; MICHAEL E. PFRENDER (Molecular Ecology, 2012)
Three mantras often guide species and ecosystem management: (i) for preventing invasions by harmful species, ‘early detection and rapid response’; (ii) for conserving imperilled native species, ‘protection of biodiversity hotspots’; and (iii) for assessing biosecurity risk, ‘an ounce of prevention equals a pound of cure.’ However, these and other management goals are elusive when traditional sampling tools (e.g. netting, traps, electrofishing, visual surveys) have poor detection limits, are too slow or are not feasible. One visionary solution is to use an organism’s DNA in the environment (eDNA), rather than the organism itself, as the target of detection. In this issue of Molecular Ecology , Thomsen et al. (2012) provide new evidence demonstrating the feasibility of this approach, showing that eDNA is an accurate indicator of the presence of an impressively diverse set of six aquatic or amphibious taxa including invertebrates, amphibians, a fish and a mammal in a wide range of freshwater habitats. They are also the first to demonstrate that the abundance of eDNA, as measured by qPCR, correlates positively with population abundance estimated with traditional tools. Finally, Thomsen et al. (2012) demonstrate that next‐generation sequencing of eDNA can quantify species richness. Overall, Thomsen et al. (2012) provide a revolutionary roadmap for using eDNA for detection of species, estimates of relative abundance and quantification of biodiversity.

Influence of year and genetic factors on chilling injury susceptibility in peach (Prunus persica (L.) Batsch) - Pedro J. Martínez-García; Cameron P. Peace; Dan E. Parfitt; Ebenezer A. Ogundiwin; Jonathan Fresnedo-Ramírez; Abhaya M. Dandekar; Thomas M. Gradziel; Carlos H. Crisosto (Euphytica, 2012)

Ethanol withdrawal-induced motor impairment in mice - Scott D. Philibin; Andy J. Cameron; Jason P. Schlumbohm; Pamela Metten; John C. Crabbe (Psychopharmacology, 2012)

Lake levels in the Erie Basin of the Laurentian Great Lakes - C. F. M. Lewis; G. D. M. Cameron; T. W. Anderson; C. W. Heil; P. L. Gareau (Journal of Paleolimnology, 2012)

Perchlorate Depositional History as Recorded in North American Ice Cores from the Eclipse Icefield, Canada, and the Upper Fremont Glacier, USA - Balaji Anandha Rao; Cameron P. Wake; Todd Anderson; William Andrew Jackson (Water, Air, & Soil Pollution, 2012)

High frequency variability of the Atlantic meridional overturning circulation - B. Balan Sarojini; J. M. Gregory; R. Tailleux; G. R. Bigg; A. T. Blaker; D. R. Cameron; N. R. Edwards; A. P. Megann; L. C. Shaffrey; B. Sinha (Ocean Science, 2011)
We compare the variability of the Atlantic meridional overturning circulation (AMOC) as simulated by the coupled climate models of the RAPID project, which cover a wide range of resolution and complexity, and observed by the RAPID/MOCHA array at about 26° N. We analyse variability on a range of timescales, from five-daily to interannual. In models of all resolutions there is substantial variability on timescales of a few days; in most AOGCMs the amplitude of the variability is of somewhat larger magnitude than that observed by the RAPID array, while the time-mean is within about 10 % of the observational estimate. The amplitude of the simulated annual cycle is similar to observations, but the shape of the annual cycle shows a spread among the models. A dynamical decomposition shows that in the models, as in observations, the AMOC is predominantly geostrophic (driven by pressure and sea-level gradients), with both geostrophic and Ekman contributions to variability, the latter being exaggerated and the former underrepresented in models. Other ageostrophic terms, neglected in the observational estimate, are small but not negligible. The time-mean of the western boundary current near the latitude of the RAPID/MOCHA array has a much wider model spread than the AMOC does, indicating large differences among models in the simulation of the wind-driven gyre circulation, and its variability is unrealistically small in the models. In many RAPID models and in models of the Coupled Model Intercomparison Project Phase 3 (CMIP3), interannual variability of the maximum of the AMOC wherever it lies, which is a commonly used model index, is similar to interannual variability in the AMOC at 26° N. Annual volume and heat transport timeseries at the same latitude are well-correlated within 15–45° N, indicating the climatic importance of the AMOC. In the RAPID and CMIP3 models, we show that the AMOC is correlated over considerable distances in latitude, but not the whole extent of the North Atlantic; consequently interannual variability of the AMOC at 50° N, where it is particularly relevant to European climate, is not well-correlated with that of the AMOC at 26° N, where it is monitored by the RAPID/MOCHA array.

Early Events of HIV-1 Infection: Can Signaling be the Next Therapeutic Target? - Kate L. Jones; Redmond P. Smyth; Cândida F. Pereira; Paul U. Cameron; Sharon R. Lewin; Anthony Jaworowski; Johnson Mak (Journal of Neuroimmune Pharmacology, 2011)

Temperature, compression and fragmentation: an experimental analysis to assess the impact of taphonomic processes on charcoal preservation - Carla Lancelotti; Marco Madella; P. Ajithprasad; Cameron A. Petrie (Archaeological and Anthropological Sciences, 2010)

The effects of secondary task interference on shape reproduction - Blake Cameron Wesley Martin; Denise Y. P. Henriques (Experimental Brain Research, 2010)

Dung pads increase pasture production, soil nutrients and microbial biomass carbon in grazed dairy systems - Sharon Rose Aarons; Catherine R. O’Connor; Hossein M. Hosseini; Cameron J. P. Gourley (Nutrient Cycling in Agroecosystems, 2009)

Pyruvate dehydrogenase phosphatase 1 (PDP1) null mutation produces a lethal infantile phenotype - J. M. Cameron; M. Maj; V. Levandovskiy; C. P. Barnett; S. Blaser; N. MacKay; J. Raiman; A. Feigenbaum; A. Schulze; B. H. Robinson (Human Genetics, 2009)

Threatened and uncommon plants of New Zealand (2008 revision) - P. J. de Lange; D. A. Norton; S. P. Courtney; P. B. Heenan; J. W. Barkla; E. K. Cameron; R. Hitchmough; A. J. Townsend (New Zealand Journal of Botany, 2009)
A reappraisal of the conservation status of the indigenous New Zealand vascular plant flora is presented using the 2008 version of the threat classification system developed for the New Zealand Department of Conservation. The list comprises 897 taxa (38% of New Zealand's total indigenous vascular flora) in the following categories: Extinct—6 taxa, Threatened—180 taxa (comprising 91 Nationally Critical taxa, 45 Nationally Endangered, and 44 Nationally Vulnerable), At Risk—651 taxa (comprising 83 Declining, 6 Recovering, 20 Relict, and 542 Naturally Uncommon taxa), 25 taxa listed as either Vagrant (12) or Coloniser (13), and 35 as Data Deficient. A further 171 plants are listed as taxonom ically indeterminate, being those which might warrant further conservation attention once their taxonomic status is clarified. Forty‐four recognised taxa and 26 plants rated as taxonomically indeterminate, and previously considered to be threatened and/or uncommon, are removed from this updated listing. A brief analysis of the patterns of rarity exhibited by the listed taxa is presented. Overall, the conservation status of the New Zealand indigenous vascular plant flora is worsening, with 7.6% of this flora now regarded as threatened with extinction. A concordance of plants names from the 2004 listing is provided.

Development of ChillPeach genomic tools and identification of cold-responsive genes in peach fruit - Ebenezer A. Ogundiwin; Cristina Martí; Javier Forment; Clara Pons; Antonio Granell; Thomas M. Gradziel; Cameron P. Peace; Carlos H. Crisosto (Plant Molecular Biology, 2008)

Engaging Recreational Fishers in Management and Conservation: Global Case Studies - E. F. GRANEK; E. M. P. MADIN; M. A. BROWN; W. FIGUEIRA; D. S. CAMERON; Z. HOGAN; G. KRISTIANSON; P. De VILLIERS; J. E. WILLIAMS; J. POST; S. ZAHN; R. ARLINGHAUS (Conservation Biology, 2008)
Globally, the number of recreational fishers is sizeable and increasing in many countries. Associated with this trend is the potential for negative impacts on fish stocks through exploitation or management measures such as stocking and introduction of non‐native fishes. Nevertheless, recreational fishers can be instrumental in successful fisheries conservation through active involvement in, or initiation of, conservation projects to reduce both direct and external stressors contributing to fishery declines. Understanding fishers' concerns for sustained access to the resource and developing methods for their meaningful participation can have positive impacts on conservation efforts. We examined a suite of case studies that demonstrate successful involvement of recreational fishers in conservation and management activities that span developed and developing countries, temperate and tropical regions, marine and freshwater systems, and open‐ and closed‐access fisheries. To illustrate potential benefits and challenges of involving recreational fishers in fisheries management and conservation, we examined the socioeconomic and ecological contexts of each case study. We devised a conceptual framework for the engagement of recreational fishers that targets particular types of involvement (enforcement, advocacy, conservation, management design [type and location], research, and monitoring) on the basis of degree of stakeholder stewardship, scale of the fishery, and source of impacts (internal or external). These activities can be enhanced by incorporating local knowledge and traditions, taking advantage of leadership and regional networks, and creating collaborations among various stakeholder groups, scientists, and agencies to maximize the probability of recreational fisher involvement and project success.

Effects of sertoli cell-conditioned medium on ventral midbrain neural stem cells: A preliminary report - Rania Shamekh; Samuel Saporta; Don F. Cameron; Alison E. Willing; Cindy D. Sanberg; Karl Johe; P. R. Sanberg (Neurotoxicity Research, 2008)

Effects of Fungicide and Rate of Application on the Development of Isolates of Polyscytalum pustulans Resistant to Thiabendazole and on the Control of Skin Spot - S. F. Carnegie; A. M. Cameron; P. Haddon (Potato Research, 2008)

Checklist of dicotyledons, gymnosperms, and pteridophytes naturalised or casual in New Zealand: Additional records 2004–06 - P. B. Heenan; P. J. de Lange; E. K. Cameron; B. S. Parris (New Zealand Journal of Botany, 2008)
New records of Naturalised and Casual plants are reported for the flora of New Zealand during the 3 yr period 2004–06. Six species are reported as fully naturalised and 162 taxa are considered to be new records of casual plants. To reflect the modes of establishment of weeds in the Casual category, and to enhance the information content of the new Casual records, we propose a new classification scheme that further subdivides this into Cultivation escape, Spontaneous Occurrence, garden Discard, and Intentional Release.

Quantitative Genetics of Traits Indicative of Biomass Production and Heterosis in 34 Full-sib F1 Salix eriocephala Families - Kimberly D. Cameron; Ingrid S. Phillips; Richard F. Kopp; Timothy A. Volk; Charles A. Maynard; Lawrence P. Abrahamson; Lawrence B. Smart (BioEnergy Research, 2008)

The Mitochondrial Genome of the Screamer Louse Bothriometopus (Phthiraptera: Ischnocera): Effects of Extensive Gene Rearrangements on the Evolution of the Genome - Stephen L. Cameron; Kevin P. Johnson; Michael F. Whiting (Journal of Molecular Evolution, 2007)

Contrasting instruction change with response change in task switching - Ian G. M. Cameron; Masayuki Watanabe; Douglas P. Munoz (Experimental Brain Research, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Past and future changes in climate and hydrological indicators in the US Northeast - Katharine Hayhoe; Cameron P. Wake; Thomas G. Huntington; Lifeng Luo; Mark D. Schwartz; Justin Sheffield; Eric Wood; Bruce Anderson; James Bradbury; Art DeGaetano; Tara J. Troy; David Wolfe (Climate Dynamics, 2007)

Remarkable Amphibian Biomass and Abundance in an Isolated Wetland: Implications for Wetland Conservation - J. WHITFIELD GIBBONS; CHRISTOPHER T. WINNE; DAVID E. SCOTT; JOHN D. WILLSON; XAVIER GLAUDAS; KIMBERLY M. ANDREWS; BRIAN D. TODD; LUKE A. FEDEWA; LUCAS WILKINSON; RIA N. TSALIAGOS; STEVEN J. HARPER; JUDITH L. GREENE; et al. (Conservation Biology, 2006)
Despite the continuing loss of wetland habitats and associated declines in amphibian populations, attempts to translate wetland losses into measurable losses to ecosystems have been lacking. We estimated the potential productivity from the amphibian community that would be compromised by the loss of a single isolated wetland that has been protected from most industrial, agricultural, and urban impacts for the past 54 years. We used a continuous drift fence at Ellenton Bay, a 10‐ha freshwater wetland on the Savannah River Site, near Aiken, South Carolina (U.S.A.), to sample all amphibians for 1 year following a prolonged drought. Despite intensive agricultural use of the land surrounding Ellenton Bay prior to 1951, we documented 24 species and remarkably high numbers and biomass of juvenile amphibians (>360,000 individuals; >1,400 kg) produced during one breeding season. Anurans (17 species) were more abundant than salamanders (7 species), comprising 96.4% of individual captures. Most (95.9%) of the amphibian biomass came from 232095 individuals of a single species of anuran (southern leopard frog [Rana sphenocephala ]). Our results revealed the resilience of an amphibian community to natural stressors and historical habitat alteration and the potential magnitude of biomass and energy transfer from isolated wetlands to surrounding terrestrial habitat. We attributed the postdrought success of amphibians to a combination of adult longevity (often >5 years), a reduction in predator abundance, and an abundance of larval food resources. Likewise, the increase of forest cover around Ellenton Bay from 60% in 2001 probably contributed to the long‐term persistence of amphibians at this site. Our findings provide an optimistic counterpoint to the issue of the global decline of biological diversity by demonstrating that conservation efforts can mitigate historical habitat degradation.

The systematic value of pollen morphology in Smilacaceae - S.-C. Chen; X.-P. Zhang; S.-F. Ni; C.-X. Fu; K. M. Cameron (Plant Systematics and Evolution, 2006)

A new location for the Poor Knights spleenwort ( Asplenium pauperequitum, Aspleniaceae) on The Forty Fours, Chatham Islands, New Zealand - E.K. Cameron; P.J. de Lange; L. R. Perrie; P. J. Brownsey; H. J. Campbell; G. A. Taylor; D. R. Given; R. M. Bellingham (New Zealand Journal of Botany, 2006)
Documentation is made of the discovery of the Poor Knights spleenwort, ( Asplenium pauperequitum ) in a sample of vascular plant specimens collected from The Forty Fours. These islands are the easternmost outlier of the Chatham Islands archipelago. Hitherto this fern had been believed endemic to the Poor Knights Islands and Mokohinau Islands of the Hauraki Gulf, off eastern Northland, North Island, New Zealand. Frond and spore morphology together with chloroplast DNA sequences were used to confirm its identity. Whether this fern disjunction of some 1245 km is the result of vicariance or longdistance dispersal is discussed and long‐distance dispersal of fern spores or whole sporangia is considered most likely.

Vascular flora of Norfolk Island: Some additions and taxonomic notes - P. J. de Lange; R. O. Gardner; W. R. Sykes; G. M. Crowcroft; E. K. Cameron; F. Stalker; M. L. Christian; J. E. Braggins (New Zealand Journal of Botany, 2005)
A total of 75 taxa (including 1 hybrid) are reported as new to the flora of the Norfolk Island group, in the south‐west Pacific Ocean. Of these 1 is endemic (Achyranthes margaretarum ), and 10 (2 pteridophytes, 8 anthophytes) taxa are considered indigenous and appear to represent either new natural long‐distance colonisations of Norfolk Island group from Australia and New Zealand or are new identifications of indigenous taxa either treated under other indigenous names or as naturalised in the Norfolk Flora. The remaining 64 taxa are considered naturalisations from resident gardens, or recent arrivals via human traffic from Australia or New Zealand. Aside from these records we discuss and update information on a further 27 taxa either covered by the last Norfolk Island flora treatment, or noted in subsequent works. A new species, Geranium gardneri , is described and treated as indigenous to Australia and naturalised in Norfolk I. and New Zealand. Nephrolepis flexuosa is reinstated for the non‐tuberous, high‐polyploid fern previously included within a broad circumscription of N. cordifolia , and which is indigenous at least to Norfolk I., Raoul I., Lord Howe I., New Zealand, and Fiji. The new combination Boehmeria australis subsp. dealbata is made for the Raoul I. (Kermadec Islands group) endemic, and Elymus multiflorus subsp. kingianus for the Norfolk and Lord Howe Island wheatgrass. The New Zealand Cordyline kaspar and Raoul I. Rhopalostylis cheesemanii are relegated to synonymy within the Norfolk I. Cordyline obtecta and Rhopalostylis baueri , respectively, which are now no longer considered endemic. Dianella intermedia and Pennantia endlicheri are treated as endemic to Norfolk I. and Senecio australis as indigenous. Two species, Ipomoea cairica and Oxalis exilis , previously treated as naturalised are recognised as indigenous, while Homalanthus populifolius is now considered naturalised and so is excluded from the indigenous flora. Anew treatment for Norfolk I. Oxalis Sect. Corniculatae is offered, and three of the four taxa reported from the island group but treated by the current flora as part of O. corniculata sens. lat. are recognised at species rank. Of these we consider only one, O. exilis , to be indigenous, and treat O. choonodes and O. radicosa as probably naturalised. We also report the first naturalised occurrence of O. corniculata sens. str. from the island group and exclude O. perennans from the flora. Isolepis cernua var. setiformis is recognised for the Norfolk I. Isolepis previously treated as probably endemic and unnamed.

Checklist of dicotyledons, gymnosperms, and pteridophytes naturalised or casual in New Zealand: Additional records 2001–2003 - P.B. Heenan; P. J. de Lange; E. K. Cameron; C. C. Ogle; P.D. Champion (New Zealand Journal of Botany, 2004)
New records of fully naturalised and casual plants are reported for the flora of New Zealand during the 3‐year period 2001–2003. Ten species are reported as additional or newly substantiated fully naturalised, 92 taxa are considered to be new records of casual plants, and 13 additional species that were previously known from few collections are given extended distributions.

First records of the Australian blenny, Omobranchus anolius , from New Zealand - Malcolm P. Francis; Peter J. Smith; Cameron Walsh; Martin F. Gomon (New Zealand Journal of Marine and Freshwater Research, 2004)
Twenty‐four blennies collected in east Auckland, New Zealand, were identified as the Australian oyster blenny, Omobranchus anolius using taxonomic and molecular characters. This species appears to have been introduced recently to New Zealand. Auckland oyster blennies mainly inhabited dead oyster shells in water pooled under intertidal boulders on mudflats. Specimens ranged from small juveniles to large mature males, suggesting that the species is breeding in New Zealand, or that there have been multiple incursion events. Oyster blennies may be capable of colonising estuaries throughout the northern North Island, and possibly farther south. Control or eradication of O. anolius would be facilitated by its intertidal habitat, lack of an escape response when found, and the very limited movement and natural dispersal of adults and larvae.

Nest architecture and genetic differentiation in a species complex of Australian stingless bees - P. FRANCK; E. CAMERON; G. GOOD; J.‐Y. RASPLUS; B. P. OLDROYD (Molecular Ecology, 2004)
We investigated the taxonomic significance of nest shape and its putative role in speciation in Trigona ( Heterotrigona ) carbonaria and T. ( H. ) hockingsi , two sibling species of stingless bee species from eastern Australia. These species are primarily distinguished by their nest architecture, as in all other respects they are nearly identical. We genotyped 130 colonies from six locations in Queensland at 13 microsatellite loci together with 106 additional colonies from six other Indo‐Pacific Trigona species. Whether they were present in allopatry or in sympatry, colonies that displayed the T. carbonaria or the T. hockingsi nest architecture could be unambiguously differentiated at the genetic level. However, T. hockingsi colonies were classifiable into two highly differentiated paraphyletic and geographically separate populations, one in northern and one in southern Queensland. These two populations probably belong to two distinct species, T. hockingsi and T. davenporti nov. sp. Our results suggest that nest architecture characters are relevant but not sufficient criteria to identify species in this group. Consequently, modifications of nest architecture are probably not of prime importance in the speciation process of Australian stingless bees, although nest architecture differences probably result from relatively simple mechanisms. The rare interspecific hybrid colonies detected did not display a nest with an intermediate form between T. hockingsi and T. carbonaria .

Genetic structure of nest aggregations and drone congregations of the southeast Asian stingless bee Trigona collina - E. C. CAMERON; P. FRANCK; B. P. OLDROYD (Molecular Ecology, 2004)
In stingless bees, sex is determined by a single complementary sex‐determining locus. This method of sex determination imposes a severe cost of inbreeding because an egg fertilized by sperm carrying the same sex allele as the egg results in a sterile diploid male. To explore how reproductive strategies may be used to avoid inbreeding in stingless bees, we studied the genetic structure of a population of 27 colonies and three drone congregations of Trigona collina in Chanthaburi, Thailand. The colonies were distributed across six nest aggregations, each aggregation located in the base of a different fig tree. Genetic analysis at eight microsatellite loci showed that colonies within aggregations were not related. Samples taken from three drone congregations showed that the males were drawn from a large number of colonies (estimated to be 132 different colonies in our largest swarm). No drone had a genotype indicating that it could have originated from the colony that it was directly outside. Combined, these results suggest that movements of drones and possibly movements of reproductive swarms among colony aggregations provide two mechanisms of inbreeding avoidance.

Genetic diversity revealed in the apomictic fruit species Garcinia mangostana L. (mangosteen) - Carl M. Ramage; Lillian Sando; Cameron P. Peace; Bernard J. Carroll; Roderick A. Drew (Euphytica, 2004)

Natural enemy specialization and the period of population cycles - P. Rohani; H.J. Wearing; T. Cameron; S.M. Sait (Ecology Letters, 2003)
The dynamical consequences of multiple‐species interactions remain an elusive and fiercely debated topic. Recently, Murdoch and colleagues proposed a general rule for the dynamics of generalist natural enemies: when periodic, they exhibit single generation cycles (SGCs), similar to single species systems. This contrasts markedly with specialists, which tend to show classic (longer period) consumer–resource cycles. Using a well‐studied laboratory system, we show that this general rule is contradicted when we consider resource age‐structure.

Invasion of the Asian goby, Acentrogobius pflaumii , into New Zealand, with new locality records of the introduced bridled goby, Arenigobius bifrenatus - Malcolm P. Francis; Cameron Walsh; Mark A. Morrison; Crispin Middleton (New Zealand Journal of Marine and Freshwater Research, 2003)
The Asian goby, Acentrogobius pflaumii (Bleeker, 1853), is reported from New Zealand waters for the first time. It was collected by beach seine in 2001–02 from muddy substrata in the upper reaches of the Waitemata and Whangapoua Harbours. We suggest that A. pflaumii has been introduced to New Zealand, probably in ship ballast water. It may have arrived directly from its native range in the north‐west Pacific Ocean, or indirectly via Australia, which it invaded before 1996. The Australian bridled goby, Arenigobius bifrenatus (Kner, 1865), which is also thought to have invaded New Zealand via ballast water, is here recorded from three new locations, extending its known New Zealand range to five different harbours spanning c. 150 km of coastline. This species is more widespread than previously thought and appears well established. Both gobies have been found only on the east coast of the North Island.

UCP3 protein expression is lower in type I, IIa and IIx muscle fiber types of endurance-trained compared to untrained subjects - A. Russell; G. Wadley; M. Hesselink; G. Schaart; S. Lo; B. Léger; A. Garnham; E. Kornips; D. Cameron-Smith; J.-P. Giacobino; P. Muzzin; R. Snow; et al. (Pflügers Archiv - European Journal of Physiology, 2003)

A new species of Olearia (Asteraceae) from Waima Forest, Northland, New Zealand - P. B. Heenan; E. K. Cameron (New Zealand Journal of Botany, 2002)
Olearia crebra is described as a new species. It is distinguished from other New Zealand species of Olearia by a set of characters including large leaves and the capitula having numerous involucral bracts, florets, and ray florets. O. crebra is restricted to montane parts of Waima Forest, western Northland, where it occurs on Hauturu, Te Raupua, Mt Misery, and upper Whirinaki Valley. As the populations of O. crebra are small and localised, and because there is a continuing need to manage browsing mammals in Waima Forest, it is listed as a Nationally Endangered species.

Checklist of dicotyledons, gymnosperms, and pteridophytes naturalised or casual in New Zealand: Additional records 1999–2000 - P. B. Heenan; P. J. de Lange; E. K. Cameron; P. D. Champion (New Zealand Journal of Botany, 2002)
Six species are reported as additional or newly substantiated fully naturalised records for the flora of New Zealand during the 2‐year period 1999–2000. Seventy‐one species are considered to be new records of casual naturalised plants. Thirty‐five additional species that were previously known from few collections are given extended distributions. A list is also provided of fully naturalised taxa that have made significant range expansions, e.g., were previously known from only one of the main New Zealand islands, but which now occur on the other island. For a number of taxa discussion is presented on their indigenous or naturalised status.

Characterization of the expressed immunoglobulin IGHV repertoire in the New World marmoset Callithrix jacchus - Hans-Christian Büdingen; Stephen L. Hauser; Cameron B. Nabavi; Claude P. Genain (Immunogenetics, 2001)

Variability of Sea-Ice Extent in Baffin Bay over the Last Millennium - Nancy S. Grumet; Cameron P. Wake; Paul A. Mayewski; Gregory A. Zielinski; Sallie I. Whitlow; Roy M. Koerner; David A. Fisher; James M. Woollett (Climatic Change, 2001)

Effect of three contrasting onion ( Allium cepa L.) production systems on nitrous oxide emissions from soil - T.J. van der Weerden; R. R. Sherlock; P. H. Williams; K. C. Cameron (Biology and Fertility of Soils, 2000)

Precipitation fluctuations in the Nepal Himalaya and its vicinity and relationship with some large scale climatological parameters - Arun B. Shrestha; Cameron P. Wake; Jack E. Dibb; Paul A. Mayewski (International Journal of Climatology, 2000)

Sucrose utilization during potato microtuber growth in bioreactors - W. -C. Yu; P. J. Joyce; D. C. Cameron; B. H. McCown (Plant Cell Reports, 2000)

Threatened and uncommon plants of New Zealand - P. J. de Lange; P. B. Heenan; D. R. Given; D. A. Norton; C. C. Ogle; P. N. Johnson; E. K. Cameron (New Zealand Journal of Botany, 1999)
A reappraisal of the conservation status of New Zealand's threatened and uncommon vascular plants is presented. The list comprises 511 taxa (22% of New Zealand's indigenous vascular flora) in the following categories: Presumed Extinct 5 taxa, Threatened 107 taxa (comprising 24 taxa Critically Endangered, 33 taxa Endangered, 50 taxa Vulnerable), Declining 60 taxa, Recovering 17 taxa (comprising 14 taxa Conservation Dependent and 3 taxa undergoing Natural Population Recovery), Naturally Uncommon 204 taxa (comprising 62 taxa rated as Sparse, 17 taxa Vagrant, 125 taxa Range Restricted). Lack of information on the threat status of a further 26 taxa caused these to be listed as Insufficiently Known. Ninety‐two taxa are listed as Taxonomically Indeterminate, being those which probably belong in one or other of the preceding lists but which are currently unnamed or where there are other doubts about their taxonomic status. About half of the Taxonomically Indeterminate taxa are probably threatened. Thirty‐three taxa formerly considered at risk are removed from the threatened and uncommon vascular plant lists. A concordance of plant names is provided.

Nitrous oxide emissions and methane oxidation by soil following cultivation of two different leguminous pastures - T. J. van der Weerden; R. R. Sherlock; P. H. Williams; K. C. Cameron (Biology and Fertility of Soils, 1999)

Surface-sediment and epilithic diatom pH calibration sets for remote European mountain lakes (AL:PE Project) and their comparison with the Surface Waters Acidification Programme (SWAP) calibration set - N. G. Cameron; H. J. B. Birks; V. J. Jones; F. Berges; J. Catalan; R. J. Flower; J. Garcia; B. Kawecka; K. A. Koinig; A. Marchetto; P. Sánchez-Castillo; R. Schmidt; et al. (Journal of Paleolimnology, 1999)

The vascular flora of Aorangi Island, Poor Knights Islands, northern New Zealand - P. J. de Lange; E. K. Cameron (New Zealand Journal of Botany, 1999)
An annotated vascular flora of 282 taxa for Aorangi Island, Poor Knights Islands, is presented. Additional records (20 taxa) from Tawhiti Rahi Island, the other major island in the archipelago, are listed separately, resulting in a combined Poor Knights vascular flora of 302 taxa. Two new combinations, Wahlenbergia littoricola subsp. vernicosa and Xeronema callistemon f bracteosa , are made for plants previously treated as W. vernicosa and X. callistemon var. bracteosa , respectively. Only one taxon, Xeronema callistemon f. bracteosa , is provisionally accepted as endemic to the Poor Knights Islands. The control of the more serious weed species on the island is discussed. A case is made for including the Mokohinau Islands within the Poor Knights Ecological Region.

Alectryon excelsus subsp. grandis (Sapindaceae): A new combination for an uncommon small tree endemic to the Three Kings Islands, New Zealand - P. J. de Lange; E. K. Cameron; B. G. Murray (New Zealand Journal of Botany, 1999)
A new combination Alectryon excelsus subsp. grandis is made for the Three Kings Islands taxon first described by Cheeseman as Alectryon excelsus var. grandis , but later raised to specific rank by him as A. grandis . Descriptions of the subspecies, its differences from A. excelsus subsp. excelsus , distribution, ecology, and chromosome counts of the subspecies are provided. A lectotype is selected for A. excelsus subsp. grandis and its conservation status reviewed.

Release of sulphate, potassium, calcium and magnesium from spent mushroom compost under laboratory conditions - D. P. C. Stewart; K. C. Cameron; I. S. Cornforth; B. E. Main (Biology and Fertility of Soils, 1997)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Genetic relationships within and between clonal and solitary forms of the sea anemone Anthopleura elegantissima revisited: evidence for the existence of two species - C. S. McFadden; R. K. Grosberg; B. B. Cameron; D. P. Karlton; D. Secord (Marine Biology, 1997)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

The effects of ultraviolet and ionizing radiation on herpesviruses, SV 40 and adenoviruses in relation to the small-plaque effect - K. R. Cameron; Lesley M. Tomkins; R. P. Eglin; L. J. N. Ross; P. Wildy; W. C. Russell (Archives of Virology, 1979)